Coating composition
Patent Information
- Application Number
- JP2024547651
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-15
- Filing Date
- 2023-02-14
- Publication Date
- 2025-03-07
AI Technical Summary
【0030】 本発明の利点 本発明者らは、特定の粒度分布を有するフライアッシュを塗料組成物中でTiO2と組み合わせて使用することにより、色への影響が小さい一方で優れた隠蔽力を有するなど、優れた光学特性を有する塗料組成物を提供できることを見出した。この特定のフライアッシュとTiO2の組み合わせにより、より低いレベルのTiO2を使用して、コントラスト比や白色度性能などの光学的利点を実現できる。
Smart Images

Figure 2025506183000001 
Figure 2025506183000002 
Figure 2025506183000003
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Application No. 63 / 309,732, filed February 14, 2022, U.S. Provisional Application No. 63 / 398,015, filed August 15, 2022, U.S. Provisional Application No. 63 / 398,037, filed August 15, 2022, U.S. Provisional Application No. 63 / 398,042, filed August 15, 2022, European Patent Application No. 22162780.5, filed March 17, 2022, and European Patent Application No. 22190437.8, filed August 15, 2022, each of which is incorporated by reference in its entirety herein. [Technical field]
[0002] The present invention relates to a coating composition. The coating composition comprises TiO2 and fly ash. The coating composition has good physical properties and good performance, such as good opacity, wet scrub resistance, hardness, abrasion resistance, and durability. The coating composition also has good moisture resistance and accelerated weathering resistance. The present invention also provides environmental benefits by increasing the utilization of fly ash, which is a common waste product. [Background technology]
[0003] Titanium dioxide is used in paint compositions to provide high opacity and a high refractive index. However, titanium dioxide is a relatively expensive material. Also, while titanium dioxide is useful for providing high opacity and brightness, titanium dioxide does not improve other properties of the paint composition. Paint manufacturers are continually working to improve the efficiency of titanium dioxide.
[0004] One way to maximize the efficiency of TiO2 is to include "extender" or "spacer" particles. Typically, these particles increase the light scattering of titanium dioxide, enhancing its efficiency.
[0005] The other particles improve the performance and weight efficiency of the pigment particles and / or the opacity of the paint. The other particles are primarily volume fillers and / or may improve the physical robustness of the paint.
[0006] Paints also need to have certain rheological properties so that they are easy to use and apply. The rheology of the paint is a factor that limits the amount of fillers and other solid particles that can be included in a paint composition. If the paint is too viscous, it is not easy to apply and does not easily form a smooth film. In addition, paints generally need to be pseudoplastic to prevent dripping after application, ensure good stability, and prevent or minimize syneresis. In general, pseudoplastic paints have a relatively low apparent viscosity when exposed to shear, but a relatively high apparent viscosity when not exposed to shear.
[0007] Other paint ingredients act as simple volume fillers or improve the opacity of the paint layer. Powder particles also provide the paint with physical robustness, e.g. abrasion resistance. Some materials may perform more than one function. Many paints contain significant amounts of these fillers (e.g. 20% or more). Common fillers include calcium carbonate and calcium sulfate. Fillers such as calcium carbonate require significant effort and processing to be made into a form suitable for use. Water-based emulsion paints are usually neutral to alkaline in pH to keep the solid particles dispersed.
[0008] As well as being effective in terms of final colour and appearance, the coating must be robust after application. The coating must have suitable optical and surface texture properties. The coating must be easy to apply.
[0009] The inventors have found that fly ash can be used in coating compositions to provide many benefits, especially when controlled to an appropriate particle size (such as by milling). Fly ash can be used as an effective spacer, opacifier, extender, and cost-effective filler to increase the abrasion resistance of coatings. The use of fly ash can reduce the amount of TiO2 required.
[0010] By controlling the particle size of the fly ash, the fly ash particles can act as an effective spacer for the existing TiO2 particles. Fly ash with such controlled particle size also improves the abrasion resistance of the paint. Fly ash can substantially reduce the volume and / or weight of titanium dioxide required in the paint composition without substantially compromising opacity or whiteness. Further improvements in the performance of the paint composition include improved wet abrasion resistance and humidity blister resistance.
[0011] There are significant environmental benefits to not only finding uses for fly ash, but also being able to incorporate relatively high levels of fly ash into applications. Fly ash, particularly coal-fired fly ash, is a waste product that is generated in large quantities when coal is burned to generate electricity. Different boiler designs produce different types of ash due to the fuels that can be burned and additives such as limestone that are added to the coal. Fly ash is typically generated from older generation pulverized-coal combustion (PCC) plants or newer fluidized-bed combustion (FBC) plants. Much of this fly ash, especially the finer fly ash, is used as a pozzolana, but much of the rest ends up in landfills and other waste disposal sites. The scale of the fly ash waste problem is so large that literally thousands of square miles of land are covered by fly ash disposal sites.
[0012] Therefore, there is a constant need to find further uses for waste fly ash to minimize ash disposal problems, both for currently produced fly ash and for fly ash mined from old dumps. Replacing raw materials used in other processes with waste fly ash has clear environmental and often economic advantages.
[0013] The present invention provides coating compositions comprising fly ash and TiO2. The coating compositions of the present invention exhibit demonstrable uses and performance advantages in many coating applications, including architectural coatings, coil coatings, powder coatings, and traffic sign coatings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Architectural Coatings Architectural coatings are used worldwide and over the last 30-40 years there has been a shift from solvent-based to water-based systems due to environmental benefits and a significant reduction in odors after a surface is painted. These coatings are typically complex mixtures of many components that must be compatible until applied to the surface and provide a desirable aesthetic to the consumer after drying. In addition to color and gloss, the most important cosmetic benefits are covering and hiding defects in the substrate as well as providing a consistent film free of defects for a pleasing presentation to the consumer.
[0015] To provide desirable post-application appearance benefits, these coatings are usually complex mixtures of binders, fillers, opacifying pigments including titanium dioxide (TiO2), and / or colorants. Additionally, most water-based coatings contain dispersants to facilitate pigment dispersion and stability, surfactants to aid compatibility between materials with different surface tensions, defoamers, biocides and / or fungicides to minimize defects, and rheology control additives for both in-can stability and to obtain desired application properties such as sag resistance and spatter resistance. Additionally, these coatings must have good flow and leveling properties on many surfaces when applied to vertical or horizontal substrates, which may include, but are not limited to, wallboard, cementitious substrates, stucco, plaster, plastics, wood, and wood products. In different parts of the world, coating thickness varies based on consumer preferences. Wall paints, for example, are typically about 40-50 microns thick, and even at such thin films (mainly provided by TiO2 or a combination of TiO2 and color pigments) very good hiding power is required. In contrast, for example, film thicknesses in Europe exceed 75 microns, and hiding power is typically based on TiO2 and optionally large amounts of fillers, such as calcium carbonate and color pigments. In all markets, additional fillers include kaolin clay, neptheline cyanite, barium sulfate, calcium carbonate, calcium sulfate, calcium silicate, gypsum, dolomite, mica, kaolin (including calcined kaolin), talc, quartz, feldspar, diatomaceous earth, aluminosilicates, aluminum oxide, wollastonite, precipitated barium sulfate (synthetic barium sulfate), lithophone (zinc sulfide-barium sulfate), etc.
[0016] While all materials in a waterborne formulation are carefully selected and often vary widely between coating platforms, the primary performance choice is usually the binder. The binder is the critical material that most impacts how the coating behaves while it is applied to the surface, but also holds all the ingredients in place after drying, bonds the coating to the surface, and contributes significantly to hiding power and durability as determined by scrub resistance, hydrophobic and hydrophilic stain resistance, burnish resistance, and touch-up properties. The most widely employed binder systems are based on acrylic monomer backbones. In the United States, the most commonly employed acrylic monomer is butyl acrylate, with additional monomers employed for lower cost based on vinyl acetate monomer, and for higher performance utilizing other acrylic monomers (e.g., ethyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, and many others). Ethylene-vinyl acetate copolymer systems are also used for higher cost, higher performance applications. In Europe, the dominant monomer system is styrene-acrylic, with performance improved by polymerizing other monomers. These systems are also used in other parts of the world, with the amounts varying according to local consumer cost and performance requirements. These chemicals are classified as carboxylates and there are a large number of them.
[0017] The hiding power of the surface, an important performance attribute, is controlled by the pigment used. TiO2 is a widely used pigment, with lighter colors used in higher amounts than darker colors, and also with variations in film thickness. The latest improvement in thin film coatings is the integration of primer and finishing topcoat coatings, reducing the number of times a surface needs to be painted to complete the job. The thickness of the film also dictates the application tool used for thin films, using a spray system or roller. For speed and efficiency, high shear rheology control when applying to the surface is required, along with thin brush filaments. Thicker films usually use thicker brush filaments or even a trowel, due to the much lower shear rheology requirements.
[0018] The global architectural coatings market is the largest coatings segment by both annual sales volume and revenue. As such, there are a huge number of raw material combinations and permutations, formulated for both performance and cost to meet local consumer demands, for both interior and exterior coatings, in both water-based and solvent-based systems. There is also a growing market for homeowner do-it-yourself (DIY) coatings, which tend to have different performance and cost standards than coatings formulated for professional painters. In all these cases, however, the basic mix of raw materials remains constant, with the binder being the most important choice, along with the TiO2 and color pigment mix for hiding power, whether water-based or solvent-based. Additives such as pigment extenders and fillers, dispersants to suspend these minerals, rheology additives, defoamers, biocides, fungicides, and compatibilizers are all common in water-based systems. Exterior coatings have the additional performance requirement of weather resistance, and require additional additives for freeze-thaw resistance. Certain fly ashes are compatible with all these materials.
[0019] Coil coating (coil painting) Coil coating is a highly efficient method of producing uniform, high-quality coating finishes on metal in a continuous, automated manner. Coil coating is also known as pre-painted metal because the metal is applied before it is processed, not after. Typically, the coil coating process begins by uncoiling the metal coil, cleaning and pre-treating it, coating it on a flat, continuous sheet, heat curing it, cooling it, and recoiling it for shipment. It is then cut to the desired size and formed into its final shape at the converter. Compared to many other coating methods, coil coating is nearly 100% efficient. Coating is typically done at very high line speeds, with modern coil lines running as fast as 700 feet per minute, and can cure the applied coating in 15 to 45 seconds. Types of coating curing employed in the coil industry include thermal, infrared, induction, and UV curing. Typically, the majority of coil coating is cured using gas-fired ovens.
[0020] Coil primers and backers are typically applied much thinner than liquid, powder, dip, or electrocoat paints that are spray applied. The dry film thickness of applied primers is typically in the range of 4-6 microns, while topcoats are typically applied to a dry film thickness of 18-20 microns. In contrast to spray applied coatings, coil coated formed surfaces, for example, provide a uniform film thickness rather than the thicker films at edges, corners, and bends that are common with spray applied paints. Coil coatings are typically applied continuously to long strips or coils of metal using a roll coater. When applying topcoats, a reverse roll coater is typically used, where the coated roll rotates in the opposite direction to the moving strip, allowing for a smooth finish. Coil coatings can also be applied by extruding the paint directly onto a moving metal coil. Typical metal coils include cold and hot rolled steel, galvanized or zinc / aluminized steel, and aluminum. Coil sheet widths typically range from about 12 inches to 72 inches. Typical applications include building siding and roofs, appliances, furnace wrappers, water heater wrappers, automotive trim and under-hood components, residential trim, siding, fascia, monumental building siding and roofs, gutters and downpipes, Venetian blinds, and siding tops for above-ground swimming pools. Topcoat types include pigmented polyester-melamine, blocked isocyanate-polyester, acrylic-melamine, PVDF, and silicone-polyester-with-melamine curing types. Typical primers include acrylic, polyester-blocked isocyanate, polyester-melamine, and epoxy. The majority of coil coatings are solvent-based, with water-based primers and topcoats being used in small quantities. Powder coatings can also be formulated for application on coil coating lines using electrostatic spray or cloud chambers. The final category of coil coatings is plastisol coatings, which are composed of polyvinyl chloride resins and plasticizers.The main use of plastisol coil coatings is in the building industry.
[0021] Coil coatings require a demanding combination of performance properties, including dry film opacity, flexibility, scratch and mar resistance, hardness, chemical resistance, and durability. Many of these performance properties are provided by the polymer and curing agent. However, pigment selection is also an important criterion, as it not only contributes color and opacity, but also provides hardness, scratch resistance, and abrasion resistance. Compared to many other filler pigments, fly ash can not only serve as a replacement for titanium dioxide, but also improve mechanical properties such as scratch resistance and accelerate performance properties, which are properties required for coil coatings.
[0022] Powder Coating Powder coatings are used in a wide variety of applications due to their many attributes, including near-zero volatile organic compounds (VOCs), low flammability, low toxicity, ability to apply thick films (50-500 microns) in a single coat, ease of application to three-dimensional objects, low energy consumption compared to many other baked finishes, and ability to be formulated to provide excellent physical properties, corrosion resistance, and weather resistance. Powder coatings can be applied by a variety of means, including electrostatic spraying, powder cloud chambers (fluidized beds), electrostatic fluidized beds, flame spraying (for some thick-film thermoplastics), and in coil coating lines that use solid blocks of paint. Due to the electrostatic application method used and the nature of powder coatings, application efficiency is also very high. Care must be taken to remove any powder that becomes airborne during application, as it can cause an explosion if not properly handled. Powder coating facilities are therefore designed to avoid this hazard by proper engineering, good housekeeping, proper grounding, and the use of triboelectrically charged application systems. Powder coatings cannot be easily applied at film thicknesses less than about 25 microns. However, the benefits of powder coating far outweigh the drawbacks. Powder coatings are applied to a variety of metals including several grades of aluminum, cold or hot rolled steel (plain or blasted), and steel pre-treated with zinc or iron phosphate. In addition to application to metals, some thermosetting powder technologies can be applied to wood and plastic surfaces for low temperature cure requirements, allowing them to cure at temperatures as low as 125-160°C.
[0023] Powder coatings are thermoplastic and thermosetting. Thermosetting powder coatings often require a balance of Tg (glass transition temperature), molecular weight, and reactivity to allow the material to be processed in an extruder without crosslinking and to avoid sintering (powder adhesion, melting and fusing) during storage. Resins with Tg in the range of 30-70°C are usually acceptable. If the Tg and / or molecular weight is too high, the material becomes difficult to process. Thermoplastic resin coatings include vinyl chloride copolymers, polyolefins, polyamides (nylons), and fluoropolymers such as polyvinylidene fluoride and ethylene / chlorotrifluoroethylene copolymers. Fluoropolymers are used in applications requiring good appearance and weatherability, such as long-life applications such as extruded aluminum frames, or applications requiring good corrosion resistance. Many powder coatings are thermosetting and can contain many types of resins and crosslinkers. For example: epoxy-functional acrylics crosslinked with dicarboxylic acids, hydroxy-functional acrylics crosslinked with blocked isocyanates or aminoplasts, carboxyl-functional polyesters crosslinked with triglycidyl isocyanurate or hydroxyalkylamides, hydroxy-functional polyesters crosslinked with blocked isocyanates or aminoplasts, epoxies or epoxy-novalacs crosslinked with polyamines, dicyanamides, phenols or anhydrides, or epoxy hybrid carboxyl-functional polyesters crosslinked with bisphenol A epoxy. Of these resin types, properly designed carboxyl-functional polyesters cured with triglycidyl isocyanurate provide excellent exterior weathering and corrosion protection. Ultraviolet (UV) cured powder coatings are also available for applications such as fiberboard. In this process, a UV-cured powder coating is applied first and melted with IR heat lamps. The melted coating is then exposed to UV lamps to cure the powder coating. UV-cured powder coatings are limited by the choice of pigments used, as are other types of coatings, including solvent and water-based paints. This is because the pigment impairs the transmission of the UV light energy required to initiate curing with a UV lamp.UV curable binders include acrylated BPA epoxy resins, acrylated polyesters, and other UV curable types. Thermoset powder coatings are used in a variety of applications including automotive, product finishes, agricultural, lawn and garden equipment, building products, and general finishes requiring excellent weatherability, physical properties, and corrosion resistance. Most powder coatings are single coat systems, but some use a primer to improve performance such as corrosion resistance.
[0024] Fly ash's low oil absorption makes it easy to process in twin screw extruders. Fly ash can increase abrasion resistance, moisture resistance, reduce water absorption and increase corrosion resistance. Ultra-durable polyester TGIC type powder coatings are used in several high performance applications including ACE industrial equipment and other high performance industrial applications.
[0025] Traffic marking coating Roads, curbs, parking lots, sidewalks, airport runways, and other paved roads are coated with traffic marking paint or median strip paint. The primary colors are white and bright yellow. One of the essential attributes of traffic marking paint is its ability to reflect headlight light to oncoming drivers. Retroreflectivity is usually achieved by spraying spherical glass beads onto the wet paint immediately after the paint is applied. The primary colors are white and bright yellow. In durable white traffic marking paints, the primary pigment is titanium dioxide, while in yellow paints both titanium dioxide and organic yellow pigments are used to maximize both opacity and brightness. Paved surfaces include asphalt and concrete. In addition to reflectivity and the ability to apply glass beads immediately after paint application, other important properties include quick drying, adhesion, abrasion or wear resistance, and weather resistance. Thus, a durable traffic marking paint must be abrasion resistant (by tires, snow plows) and weather resistant (resistant to ultraviolet light, visible light, moisture, and freeze-thaw) in addition to adhesion.
[0026] Road marking paints are required to be abrasion resistant. For most traffic marking applications, the paint is applied to a dry film thickness of about 250 microns. Several types of polymer binders are used, but perhaps the most common are acrylic latexes, because their formulations can be optimized to provide cost-effective binders, low VOC, fast drying, and the required performance characteristics. Fast drying is achieved by using ammonium hydroxide neutralized acrylic latexes, which rapidly coalesce. Other types of binders include: 100% solids hot melt binders such as tall oil rosin or maleic esters of rubber resins with glass beads, these stripping paints are applied at 2500 microns and are more prevalent in warmer climates as they are prone to adhesion loss, low VOC solvent-based paints (containing acetone since in the US acetone is considered a VOC exemption), acrylic / epoxies, and alkyd resins.
[0027] The incorporation of fly ash into traffic marking coatings offers several enhanced performance characteristics, including reduced cost and potentially increased durability through improved abrasion resistance, wear resistance, and moisture resistance.
[0028] prior art JP 2014-196401 and JP 2015-074769 both relate to a thermal barrier paint coating composition. The paint composition may have hollow particles that reflect solar radiation and are said to have a thermal insulation effect. Fly ash is mentioned as one of many materials suitable for the hollow particles. The hollow particles have an average particle size of 5 to 150 μm. These hollow particles are larger than the particle size distribution of fly ash required in the present invention, and the teaching that these hollow particles need to be hollow to act as a thermal insulator is not consistent with the particle size distribution of less than 4.0 μm required in the present invention. 50 This would clearly direct one skilled in the art away from fly ash having particle sizes significantly closer to the 150 μm end of the range, and towards larger particle sizes.
[0029] These hollow particles, also known as cenospheres, are usually formed by the expansion of air trapped inside molten particles in hot gases. Cenospheres are usually quite large, e.g., greater than 30 microns, because gas trapped inside small particles easily escapes, meaning that small cenospheres rarely form.
[0030] Advantages of the Invention The inventors have found that the use of fly ash having a particular particle size distribution in combination with TiO2 in a coating composition can provide a coating composition with excellent optical properties, such as excellent hiding power with little impact on color. This particular combination of fly ash and TiO2 allows optical benefits such as contrast ratio and whiteness performance to be achieved using lower levels of TiO2.
[0031] Other advantages include good wet scrub resistance and dry rub performance, as well as good weatherability, UV protection, and other benefits. Summary of the Invention
[0032] The present invention provides a coating composition comprising: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 70 wt% TiO2; and (c) 10 wt% to 80 wt% of a polymer binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0033] A highly preferred embodiment of the present invention comprises a white paint composition comprising: (a) 3wt%-35wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 50 wt% of a solvent; and (d) 10 wt % to 30 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0034] Another highly preferred embodiment of the present invention comprises a coating composition comprising: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% of a solvent; and (d) 10 wt % to 35 wt % of a polymeric binder material selected from modified or unmodified polyacrylates; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0035] Another highly preferred embodiment of the present invention comprises a coating composition, which is an aqueous based composition (also referred to as an aqueous composition or water-based composition) and comprises: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% water, and (d) 10 wt % to 35 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0036] Another highly preferred embodiment of the present invention comprises a coating composition, which is a solvent-based composition, comprising: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 60 wt% TiO2 or other pigment; (c) 1.0 wt% to 70 wt% organic solvent; (d) 15 wt% to 80 wt% of a polymeric binder material; and (e) 3.0 wt % to 20 wt % of a crosslinker; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size. The coating compositions described above are particularly suitable for use as coil coating coatings.
[0037] Another highly preferred embodiment of the present invention comprises a coating composition, which is a powder coating composition, comprising: (a) 10wt%-40wt% fly ash; (b) 1wt%–60wt% TiO2; (c) 15 wt% to 80 wt% of a polymeric binder material; and (d) 3.0 wt % to 20 wt % of a crosslinker; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size. The coating composition described above is particularly suitable for powder coating applications.
[0038] Another highly preferred embodiment of the present invention comprises a coating composition comprising: (a) 1.0wt%-6.0wt% fly ash; (b) 1.0wt%~70wt% TiO2; (c) 20 wt% to 35 wt% water, and (d) 25 wt% to 40 wt% of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size. The above coating compositions are particularly suitable for traffic marking coating applications.
[0039] [Detailed Description of the Invention] paint composition The coating composition comprises: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 70 wt% TiO2; and (c) 10 wt% to 80 wt% of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0040] The coating composition may include the following: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 60 wt% TiO2; and (c) 10 wt% to 80 wt% of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0041] The coating composition may include the following: (a) 1.0wt%-40wt% fly ash; (b) 1.0wt%~60wt% TiO2; (c) 1.0 wt% to 70 wt%, or 1.0 wt% to 70 wt% solvent; and (d) 10 wt % to 80 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0042] A highly preferred embodiment of the present invention comprises a white paint composition comprising: (a) 3wt%-35wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 50 wt% of a solvent; and (d) 10 wt % to 30 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0043] Another highly preferred embodiment of the present invention comprises a coating composition comprising: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% of a solvent; and (d) 10 wt % to 35 wt % of a polymeric binder material selected from modified or unmodified polyacrylates; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0044] Another highly preferred embodiment of the present invention comprises a coating composition, which is an aqueous based composition and comprises: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% water, and (d) 10 wt % to 35 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0045] Another highly preferred embodiment of the present invention comprises a coating composition, which is a solvent-based composition, comprising: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 60 wt% TiO2 or other pigment; (c) 1.0 wt% to 70 wt% organic solvent; (d) 15 wt% to 80 wt% of a polymeric binder material; and (e) 3.0 wt % to 20 wt % of a crosslinker; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size. The coating composition described above is particularly suitable for coil coating applications.
[0046] Another highly preferred embodiment of the present invention comprises a coating composition, which is a powder coating composition, comprising: (a) 10wt%-40wt% fly ash; (b) 1wt%–60wt% TiO2; (c) 15 wt% to 80 wt% of a polymeric binder material; and (d) 3.0 wt % to 20 wt % of a crosslinker; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size. The coating composition described above is particularly suitable for powder coating applications.
[0047] Another highly preferred embodiment of the present invention comprises a coating composition comprising: (a) 1.0wt%-6.0wt% fly ash; (b) 1.0wt%-7.0wt% TiO2; (c) 20 wt% to 35 wt% water, and (d) 25 wt% to 40 wt% of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size. The above coating compositions are particularly suitable for traffic marking coating applications.
[0048] Preferably, the composition is a white paint composition and comprises: (a) 3wt%-35wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 50 wt% of a solvent; and (d) 10 wt% to 30 wt% of a polymeric binder material.
[0049] Preferably, the composition is an aqueous composition. Preferably, the solvent is water. Preferably, the composition contains 20 wt % to 50 wt % water. Preferably, the composition is in the form of an emulsion. The composition may include an organic solvent. Preferably, the solvent is water and the polymeric binder material is a carboxylate polymer.
[0050] Preferably, the weight ratio of fly ash to TiO2 is in the range of 1:3 to 30:1, preferably 1:1 to 30:1, or 1.5:1 to 20:1, or 2:1 to 10:1, or 2:1 to 6:1, or 2:1 to 4:1. Compositions with these weight ratios are optimized for the performance of TiO2 and are very environmentally friendly.
[0051] Alternatively, the weight ratio of fly ash to TiO2 may range from 0.6:1 to 1.5:1. Compositions having this weight ratio exhibit good wet scrub resistance and water resistance, and do not easily blister or smear.
[0052] The weight ratio of fly ash to TiO2 may be in the range of 0.05:1 to 1:1, or even 0.1:1 to 0.8:1. The weight ratio of fly ash to TiO2 may be in the range of 0.05:1 to 2:1, or 0.1:1 to 2:1, or 0.1:1 to 1.5:1, or even 0.1:1 to 0.8:1.
[0053] Preferably, the composition comprises between 10wt% and 35wt%, or between 15wt% and 35wt%, or between 20wt% and 35wt%, or between 20wt% and 30wt% of fly ash.
[0054] Typically, the composition comprises 1 wt% to 30 wt% TiO2, or 5 wt% to 20 wt% TiO2. Preferably, the composition comprises 1 wt% to 8 wt% TiO2, alternatively, the composition may comprise 15 wt% to 30 wt% TiO2.
[0055] Typically, the compositions have a viscosity in the range of 400 cP to 2500 cP, or 400 cP to 2000 cP, or 400 cP to 1750 cP, 400 cP to 1500 cP, or 500 cP to 1500 cP. The viscosity of the coating composition can be adjusted as needed, for example, to accommodate storage stability and / or various application methods (e.g., spray vs. brush). Preferably, the composition is thixotropic.
[0056] The composition may include other powder materials. The composition may include 0 wt% to 30 wt%, or 1.0 wt% to 27 wt%, or 1.0 wt% to 25 wt%, or 1 wt% to 20 wt%, or 1 wt% to 15 wt% of other powder materials.
[0057] Suitable powder materials include materials for adjusting the optical or rheological properties of the composition, and additional pigments for imparting color.
[0058] Other powdered materials include calcium carbonate and / or calcium sulfate. Other powdered materials include barium sulfate, talc, wollastonite, calcium carbonate and / or calcium sulfate, silica, quartz, mica, and any combination thereof. Other suitable powdered materials include calcium silicate and / or dolomite.
[0059] The composition may be brilliant white, but may also be a pastel off-white, particularly when the composition is a white paint composition.
[0060] Typically, white paint is the L of the paint (preferably the dried paint). * a * b * is defined by the value, where L * is greater than 80, a * and b * are independently within the range of ±10. Typically, the composition has a whiteness L value of greater than 80, or greater than 85, or greater than 90, or greater than 95. Typically, the composition has a whiteness where the a and b values are each independently within the range of -10.0 to +10.0. Typically, the composition has a hiding powder / contrast ratio of greater than 98.0, or even greater than 99.0.
[0061] The composition typically includes other ingredients. Any suitable ingredient may be included in the composition. Suitable additional ingredients are described in more detail below.
[0062] Fly Ash The fly ash has a particle size of less than 4.0 μm, preferably less than 3.5 μm, or preferably less than 3.0 μm, preferably in the range of 0.5 μm to 3.0 μm, or 1.0 μm to 2.0 μm. 50 It has a particle size. Preferably, the fly ash has a particle size of less than 12 μm, or less than 10 μm, or less than 8.0 μm, or less than 6.0 μm, or less than 5.0 μm, or less than 4.0 μm. 90 has.
[0063] It is preferred that the particle size distribution is narrow. d less than 4.0μm 50 and d in the range of 1.0μm to 2.0μm 50 Particularly preferred is fly ash having the formula: Preferably, the fly ash has a particle size of 0.1 μm to 1.5 μm, or 0.2 μm to 1.0 μm, or 0.3 μm to 0.8 μm, or 0.4 μm to 0.6 μm. 10 has. A highly preferred fly ash is milled fly ash (ground fly ash).
[0064] Preferably, the fly ash has an oil absorption of less than 40cc / 100g, or less than 35cc / 100g, or in the range of 1cc / 100g to 35cc / 100g, or in the range of 10cc / 100g to 30cc / 100g, or in the range of 20cc / 100g to 40cc / 100g, or even in the range of 20cc / 100g to 30cc / 100g. A further advantage of using fly ash compared to other possible materials is that it generally has a low oil absorption. Oil absorption is related to the porosity of the powder and its ability to adsorb liquids. The addition of sorbent powder to a paint obviously has a large effect on the rheology of the paint, since the sorbent powder "soaks up" the liquid (such as water or other solvents). This may limit the amount of useful powder that can be added to the paint to maintain the required rheology. In order to make the paint easy to apply, the viscosity of the paint should not be too high. The inherently low absorption of fly ash allows higher levels of fly ash to be added to the paint, improving wear resistance and cost without excessively increasing the paint's viscosity.
[0065] Typically, fly ash is acid treated. A preferred beneficiation process for fly ash uses acid treatment of the fly ash. A preferred fly ash is acid treated and milled (either simultaneously or sequentially). Acid treatment can remove alkaline species such as calcium oxide, other metal species such as iron salts, and can leave a roughened surface. Without wishing to be bound by theory, it is believed that particles with rough or irregular surfaces have surface pores that help trap TiO2 particles and hold them in place better, thus negating their tendency to agglomerate. Acid treatment can also reduce the level of iron (and other metal) species in the fly ash. The iron and other metal species in the fly ash give the fly ash its dark color.
[0066] Preferably, the fly ash contains less than 1.5 wt.%, or less than 1.0 wt.%, or less than 0.5 wt.% Fe2O3. Preferably, the fly ash contains less than 1.5 wt.%, or less than 1.0 wt.%, or less than 0.5 wt.% CaO.
[0067] Preferably, the fly ash has a zeta potential in the range of -20 mV to -60 mV. Typically, the zeta potential is measured at pH 7.0 and in 0.01 M NaCl aqueous solution at a solids concentration of 0.1 wt %. Typically, the whitened fly ash has an iron oxide content of less than 1.5 wt%, less than 1.0 wt%, or even less than 0.5 wt%.
[0068] Preferably, the fly ash is coal combustion fly ash, most preferably pulverized coal combustion (PCC) fly ash. The fly ash may be Type F coal fly ash. Fly ash usually has a characteristic spherical shape that allows it to be analyzed in coating compositions.
[0069] TiO 2 TiO2 comes in many polymorphs, and pigment particles are usually either anatase or rutile. Rutile is the most common. Many TiO2 pigments are surface modified to optimize certain aspects of their performance. For example, TiO2 pigments may be treated to make the surface more hydrophobic to ensure compatibility in paints that contain high levels of organic solvents. Suitable TiO2 pigments include Chemours' Ti-Pure series (e.g., Ti-Pure R906 and Ti-Pure R-706) and Venator's Tioxide series.
[0070] Depending on the surface treatment, TiO2 particles can have positive or negative zeta potential values at the typical pH of the paint. For example, R-906 titanium dioxide pigment has a positive zeta potential under conditions where fly ash has a negative zeta potential.
[0071] Suitable TiO2 include: the Ti-Pure series from Chemours, TiO2 from Kronos, the INEOS Pigments series from INEOS Enterprises, the TIOXIDE, SACHTLEBEN, DELTIO series from Venator, the TiONA series from Tronox, TiO2 from Cinkara, the Pretiox series from Precheza, TiO2 from Ishihara, the BILLIONS series from LB Group, the DeTOX series from Devine Chemicals, and the Tytanpol series from Grupa Azoty Police.
[0072] Suitable TiO2 include rutile and anatase grades of titanium dioxide. Typically, rutile titanium dioxide is preferred. The surface of the titanium dioxide may be treated with a variety of organic or inorganic surface treatments.
[0073] Without wishing to be bound by theory, a combination of fly ash extender particles and TiO2 pigment particles, where the particles have different zeta potential values [+ and -], is sometimes preferred due to increased particle interaction.
[0074] Solvent (Vehicle) The composition may contain a solvent. Preferably, the composition contains 10 wt% to 60 wt%, or 20 wt% to 50 wt% of the solvent.
[0075] The solvent can act such that the polymeric binder material is partially or completely dissolved in the solvent, or the solvent can also act as a liquid carrier material in which the polymeric binder does not dissolve, but instead forms a colloidal or separate phase from the solvent. In most cases, the solvent is water.
[0076] The solvent may be an organic solvent. Organic solvents include aliphatic hydrocarbons, such as paraffin distillates, such as white spirit. Other organic solvents include toluene, ethylbenzene, mixed xylenes, high flash naphtha, and any combination thereof. Such organic solvents are typically used in oil-based paints.
[0077] Suitable solvents include "oxygenated solvents" including species such as ketones, esters, alcohols, glycol ethers, glycol ether esters, ether esters, and the like. Such oxygenated solvents can be used for multiple purposes in paints, such as antifreeze and coalescent agents, as well as solvents. Examples of suitable glycol ether solvents include methyl carbitol (2-(2-methoxyethoxy)ethanol), ethyl carbitol, and any combinations thereof. Suitable glycol solvents include ethylene glycol, propylene glycol, hexylene glycol, and any combinations thereof. Another suitable solvent is 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate. These oxygenated solvents are also known as oxygenated hydrocarbons.
[0078] Suitable organic solvents may be oxygenated hydrocarbons that contain one or more oxygen-containing functional groups, such as esters, alcohols and / or ethers, or combinations thereof. The composition may comprise 20 wt% to 50 wt% of the oxygenated hydrocarbon. The solvent may be a mixed solvent of water and an oxygen-containing hydrocarbon. In the case of this mixed solvent system, the composition may contain 1 wt % to 20 wt % of the oxygen-containing hydrocarbon.
[0079] The solvent may be a non-aqueous solvent. Preferred non-aqueous solvents are organic solvents. Non-aqueous solvents often have adverse environmental effects if released into the environment during drying, which has led to an increase in more environmentally friendly "low VOC" (low volatile organic content) or non-VOC coating compositions, such as water-based coating compositions, and especially water-based emulsion coating compositions.
[0080] However, some solvents that decompose more readily in the atmosphere and therefore pose much less risk to the environment are regulated as "exempt" solvents that do not have to meet regulatory limits. Preferably, the solvent is an exempt solvent. Examples of exempt solvents include acetone, dimethyl carbonate, methyl acetate, parachlorobenotrifluoride, tert-butyl acetate, propylene carbonate, and any combination thereof. Such exempt solvents can be used at higher levels than non-exempt solvents. Exempt solvents can be used in coating compositions for applications where water-based solvents are not suitable.
[0081] Preferably, the solvent is selected from organic solvents, water, and combinations thereof. Preferably, the solvent is water. Preferably, the composition comprises 20wt% to 50wt% water. It is also preferred that the solvent is an organic solvent. Suitable organic solvents are aliphatic hydrocarbons. Aliphatic hydrocarbon solvents are typically used in oil-based coating compositions. The composition may include 20 wt % to 50 wt % of an organic solvent.The composition may include 20 wt % to 50 wt % of an aliphatic hydrocarbon.
[0082] Suitable solvents for solvent-based coil coatings depend on the binder and crosslinker selected. For purposes of illustration, polyester-based coil coatings are described herein as they are the most commonly used in the industry, however, other suitable coatings include acrylics, fluoroplastics, halogenated polymers, silicone polyesters, epoxies, epoxy esters, polyvinyl chloride, and the like. Solvents commonly used in coil coatings include oxygenated solvents (e.g., alcohols, ketones, esters, ethers, glycols, glycol ethers, glycol ether esters, ether esters, and the like), such as butanol, isobutanol, isopropanol, butyl cellosolve, PM acetate, diacetone alcohol, and the like, and hydrocarbons, such as, but not limited to, aromatic 100, aromatic 150, aromatic 200, VM&P naphtha, xylene, toluene, and the like.
[0083] The solvent not only solubilizes the polymeric binder material, but also serves to adjust viscosity, minimize coating defects, provide flow and leveling, or the solvent can act as a liquid carrier material in which the polymeric binder does not dissolve, but instead forms a stable dispersion of the polymeric binder in the solvent.
[0084] The solvent may be a mixture of water and a non-aqueous solvent (such as a hydrocarbon). The solvent may be a mixture of a small amount of water and an oxygen-containing hydrocarbon. In this mixed solvent system, the composition may contain 1 wt% to about 10 wt% water.
[0085] In contrast to many other coating types, the majority of coil coating lines use incineration to eliminate the introduction of solvents into the atmosphere, so there is little environmental risk. The solvent may be an exempt solvent. Examples of exempt solvents include acetone, dimethyl carbonate, methyl acetate, parachlorobenzotrifluoride, tert-butyl acetate, propylene carbonate, and any combination thereof. Such exempt solvents may be used at higher levels than non-exempt solvents.
[0086] The composition may comprise from 10 wt% to 60 wt% of an organic solvent.The composition may comprise from 20 wt% to 60 wt% of an aliphatic and / or aromatic hydrocarbon.
[0087] Polymer Binder Materials Preferably, the composition comprises 10wt% to 60wt% of the polymeric binder material, or 10wt% to 50wt%, or 10wt% to 40wt%, or 10wt% to 30wt%, or 15wt% to 30wt% of the polymeric binder material. The composition may comprise 20wt% to 40wt% of the polymeric binder material.
[0088] Preferably, the polymeric binder material is selected from a carboxylate polymer, an alkyd polymer, or a combination thereof. The polymeric binder material may be a carboxylate polymer. The polymeric binder material may be an alkyd resin.
[0089] Suitable carboxylate polymers are polycarboxylate polymers. The composition may comprise from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of the carboxylate polymer. The composition may include from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of the alkyd resin. Suitable polymeric binder materials are available from Arkema and Dow.
[0090] Carboxylate Polymers Particularly preferred polymeric binder materials are carboxylate polymers. Suitable carboxylate polymers include homopolymers, copolymers and / or terpolymers, and suitable polymers include carboxylate polymers comprising monomers selected from methanoic acid, ethanoic acid, propanoic acid, butanoic acid and any combination thereof. Particularly preferred carboxylate polymers include propanoic acid monomers and / or monomers derived from propanoic acid.
[0091] Suitable carboxylate polymers include homopolymers, copolymers and / or terpolymers selected from polyacrylates.Suitable polyacrylates include polyacrylates containing monomers selected from vinyl acrylate, ethylene-vinyl acetate-acrylic acid, styrene-acrylic acid, ethylene-vinyl acetate-acrylate, polyvinyl acetate-polyvinyl chloride-acrylate (PVC / PVAc), and methacrylates.Derivatives of these monomers are also suitable for use in polyacrylate polymers.
[0092] Suitable carboxylate polymers are those based on derivatives of acrylic or methacrylic acid (eg polyacrylates, styrene-acrylic polymers, copolymers of acrylic and methacrylic acid). Suitable carboxylate polymers include vinyl functional monomers (eg, vinyl acetate-acrylic copolymers).
[0093] A suitable carboxylate polymer is Lubrizol's Carboset® water-based latex emulsion. TM For example, Carboset CR-3090 TM Carboset 2966 is a styrene-acrylic copolymer latex emulsion with 45% solids. TM is an acrylic copolymer latex emulsion with 41-43% solids. Other suitable materials include Primal 1000 from Dow Chemical Company. TMThere is a polymer emulsion series.
[0094] Suitable carboxylate polymers include Rovene from Mallard Creek Polymers. TM Aquamac, a carboxylated acrylic copolymer latex from Polynt Composites TM Styrene-acrylic latex polymer, Acronal from BASF TM styrene-acrylic latex products; and Polynt's Synthemul vinyl-acrylic latex products.
[0095] Suitable carboxylate polymers are available from Wacker Chemie and Arkema. Suitable polymeric binder materials include Airflex EF-811, available from Wacker Chemie. Airflex EF-811 is a vinyl acetate-ethylene (VAE) copolymer emulsion.
[0096] Preferably, the polymeric binder is a carboxylate polymer. Preferably, the carboxylate polymer is in the form of a latex emulsion, preferably an aqueous latex emulsion. This is particularly preferred when the solvent is water. The carboxylates can be modified with modifying monomers to make vinyl or styrene modified acrylic latexes.
[0097] A highly preferred polymeric binder material is a carboxylate polymer. Preferably, the composition comprises from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of a carboxylate polymer. A preferred carboxylate polymer is a polyacrylate polymer or a derivative thereof.
[0098] Carboxylate polymers are usually added to coating compositions in the form of aqueous latex emulsions or dispersions (e.g., polyurethane dispersions). Such emulsions typically have a solids content of 30 wt% to 60 wt%. The size of the polymer particles in the latex is typically between 100 nm and 1000 nm.
[0099] Polycarboxylates, and especially polyacrylates, have excellent physical and chemical properties such as fire resistance, UV resistance, abrasion resistance, vapor permeability, high weatherability and gloss retention.
[0100] Some carboxylate polymers have dispersant properties and can act as dispersants. Such carboxylate polymers include homopolymers and copolymers of polycarboxylic acids (including those modified to be hydrophobic or hydrophilic), such as polyacrylic acid or polymethacrylic acid or maleic anhydride with various monomers such as styrene, methacrylate, diisobutylene, and other hydrophilic or hydrophobic comonomers. For example, for some components, the level of carboxyl functionality in these oligomers or polymers is so high that they are sufficiently polar to be dispersed in water without the addition of neutralizing amines.
[0101] Preferably, the composition comprises from 10 wt% to 30 wt%, or from 15 wt% to 25 wt% of the carboxylate polymer.
[0102] Alkyd Polymers A suitable polymeric binder material is an alkyd polymer. Generally, alkyds are vegetable oil or fatty acid modified low molecular weight polyesters obtained by condensation reaction of polyhydric alcohols, monobasic and polybasic acids, vegetable oils and fatty acids. Alkyd polymers, also commonly known as alkyd resins, are usually synthesized by esterification of suitable carboxyl and hydroxyl group containing molecules. Suitable alkyd resins include short oil, medium oil and long oil alkyds. Short oil alkyds typically contain less than 40 wt% fatty acid. Medium oil alkyds typically contain 40 wt% to 60 wt% fatty acid. Long oil alkyds typically contain more than 60 wt% fatty acid.
[0103] Alkyd resins are typically used in solvent-based coatings using hydrocarbon solvents. Suitable hydrocarbon solvents may be non-oxygenated or oxygenated. Alkyd resins may be modified to increase their compatibility with water, allowing them to be used in water-based coatings.
[0104] In some cases it may be preferred that the polymeric binder material is an alkyd resin, especially when the solvent is an organic solvent such as an aliphatic hydrocarbon. Modified alkyd polymers are also suitable. Suitable alkyd polymers are selected from silicon modified alkyd polymers. Suitable alkyd polymers can also be selected from acrylic modified alkyd polymers. An example of a suitable alkyd resin is Duramac 207-1388 from Polynt Group.
[0105] Epoxy Polymer A suitable polymeric binder material is an epoxy polymer, also commonly known as an epoxy resin. Epoxy resins are available in liquid and non-aqueous solvent types.
[0106] Suitable epoxy resins can be obtained by reacting epichlorohydrin with bisphenols. Suitable bisphenols include bisphenol A, bisphenol B and / or bisphenol F, preferably bisphenol A. A suitable epoxy resin is Ancarez AR 555 from Evonik, a water-based epoxy resin with a solids content of 55 wt %.
[0107] Epoxy resins can also be modified with many materials, including, for example, fatty acids, to make epoxy esters. An example of an epoxy ester is Ranbar 4892 sd-50 from Gabriel Performance Products. Some epoxy esters have pendant hydroxyl groups that, when exposed to elevated temperatures, can react with crosslinkers such as aminoplasts or isocyanate-functional crosslinkers, such as melamine or urea formaldehyde. Other epoxy esters, such as 4692 sd-50 from Gabriel Peformance Products, can be used in both cold and hot cure systems when a crosslinker is present.
[0108] Epoxy resins are typically blended with a hardener before being incorporated into the coating composition. Any suitable chemical may be used to cure the epoxy resin. Suitable curing agents include polyamines and polyamides. A commercially available polyamide-based epoxy hardener is Ancamide 220 from Evonik.
[0109] Suitable epoxy resins can be obtained by reacting epichlorohydrin with bisphenols. Suitable bisphenols include bisphenol A, bisphenol B and / or bisphenol F. The preferred bisphenol is bisphenol A. A suitable epoxy resin is Evonik's Ancarez AR 555, a water-based epoxy resin with 55 wt % solids. An example of a water-based epoxy resin is Evonik's Ancarez AR 555, which is a 55% solids water-based epoxy resin.
[0110] Hydroxy-functional polyesters Particularly preferred polymeric binder materials are hydroxy-functional linear or branched polyesters. Hydroxy-functional polyesters are typically synthesized with a molar excess of hydroxy functionality for reaction with aminoplasts and / or blocked or activated isocyanate crosslinkers in one- or two-component coatings. Typically, one-component formulations are more preferred for coil coating applications due to pot life issues associated with the use of isocyanate crosslinkers. Suitable hydroxy functional polyester polymers are composed of one or more diols and may include one or more triols, such as neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 1,6-hexanediol, ethylene or propylene glycol, 2,2,4-trimethyl-1,3-pentanediol, 1,4-cyclohexanedimethanol, and trimethylolpropane, as well as suitable acid or anhydride functional monomers, such as suitable carboxyl functional aliphatic, cycloaliphatic, or aromatic acids, which usually contain two or more carboxyl functional acid groups, such as adipic acid, azelaic acid, sebacic acid, cyclohexanedicarboxylic acid, isophthalic acid, phthalic acid, terephthalic acid, hexahydrophthalic anhydride, trimellitic anhydride, and the like.
[0111] Suitable hydroxy-functional polyester polymers include the use of one or more of the hydroxy- and / or carboxy-functional building blocks listed above. Polyester resins are generally formed by step-growth polymerization of one or more alcohols having at least two hydroxy groups with a carboxylic acid having at least two carboxyl groups. Other routes to polyester synthesis include reaction of esters with alcohols, reaction of anhydrides with alcohols, ring-opening polymerization of lactones, and the like. Polyesters can also be modified with reactants such as benzoic acid, monofunctional epoxy-functional reactants (e.g., glycidyl esters of versatic acid), and the like. Synthesis of polyester resins can be carried out under suitable conditions, such as temperatures of about 145 to about 260° C. A catalyst (such as dibutyltin oxide or other suitable catalyst) is typically used. The by-product is typically water, which is removed by simple distillation, vacuum distillation, or azeotropic distillation to drive the reaction to completion.
[0112] The essentially linear polyester preferably has a number average molecular weight in the range of about 4,000 to about 5,000 and a weight average molecular weight of about 5,200 to about 8,000, with a polydispersity of preferably about 1.2 to about 2.0. Suitable polyester polymers are available from a number of suppliers, examples of suitable hydroxy-functional polyester suppliers include, but are not limited to, Uralac SN844 S2G3-60 ND or Uralac SN831 S2G3-60 ND, Uralac SN804 S2-65 ND supplied by DSM, Polymac 220-1939, Polymac 66-6613 supplied by Polynt Composites, and Setal 16-1084 supplied by Allnex.
[0113] Preferably, the polymeric binder is a hydroxy-functional saturated polyester, preferably supplied in the form of a solution in a suitable oxygen-containing organic solvent or petroleum distillate. The polyester is typically supplied at a solids content of 40 wt% to 80 wt%, or 60 wt% to 75 wt%.
[0114] Suitable hydroxy-functional polyesters for use in formulated coating compositions provide good flexibility, good hardness, good adhesion, good chemical resistance, good abrasion resistance, good overbaking resistance, and good outdoor weatherability.
[0115] Preferably, the polymeric binder is a hydroxy-functional saturated polyester, preferably supplied in the form of a solution in a suitable oxygen-containing organic solvent or petroleum distillate. The polyester is typically supplied at a solids content of 40 wt% to 80 wt%, or 60 wt% to 75 wt%.
[0116] Other polymer binder materials Any suitable polymeric binder material can be used.Suitable polymeric binder materials are selected from polyesters, modified polyesters such as siliconized polyesters, especially oil-modified polyesters.Typically, such polyesters are used in combination with organic solvents, typically aliphatic hydrocarbons, and oxygen-containing organic solvents.
[0117] Other suitable polymeric binder materials are selected from: vinyl acetate-vinyl versatate; vinyl acetate-vinyl maleate; ethylene-vinyl acetate; styrene-butadiene; polyvinyl acetate; polysiloxanes; silane modified polymers; halopolymers, such as fluoropolymers (e.g., polyvinylidene fluoride, FEVE (fluorinated ethylene vinyl ether), polyvinyl chloride; polychloroprene); styrene-butadiene; polyesters; polyurethanes, particularly polyurethanes suitable for forming aqueous dispersions; polyurethane dispersions (PUDs); plastisols (PVC and plasticizer); inorganic polymer coating systems; phenolic resins such as epoxy-phenolic resins; polybutadienes, polyolefins, hybrid polymers, polyether polyols, and any combination thereof.
[0118] Suitable polymeric binder materials are available from Wacker Chemie and Arkema. Suitable polymeric binder materials include Wacker EF-811 from Wacker Chemie and Airflex from Air Products Polymers LP. [登録商標] An example is EF811.
[0119] The polymeric binder material may be a two-component (two-part) polyurethane material. Two-component polyurethane materials are widely used as coatings in many applications, such as topcoats for automotive repaints, aerospace topcoats for both civilian and military use, topcoats for offshore oil rigs, heavy duty maintenance coatings, bridge coatings, and the like. Polyurethanes can be tailored to provide a variety of performance requirements, including excellent outdoor weatherability, light stability, chemical resistance, flexibility, moisture resistance, and corrosion resistance, when applied over an epoxy primer. Two-component urethane materials use a wide variety of polymers in combination with component A and component B. Suitable component A materials include hydroxy-functional polymers, such as commonly used polyesters, acrylics, fluoropolymers, and hybrid polymers. Suitable B components include reactive prepolymers that contain reactive isocyanate functionality. The reaction of component A (polyol) with component B (isocyanate) forms a two-component polyurethane material. Exterior topcoats typically use aliphatic isocyanate prepolymers that provide good weatherability when crosslinked with the light-stable binder in component A. Aromatic isocyanate prepolymers can also be used, but are less light stable than their aliphatic isocyanate counterparts. Thus, when aromatic isocyanates are used, they are typically used for primers and / or interior applications that do not require light stability. Two-component polyurethane materials can be solvent- or water-based. Examples of polyols in component A include Joncryl 903 acrylic polyol available from BASF, Setalux 17-1084 hydroxy-functional acrylic polyol available from Allnex, Bayhydrol A 2470 water-based hydroxy-functional polyacrylic dispersion for 2K polyurethanes available from Covestro, and Lumiflon LF200F fluoroethylene vinyl ether polyol available from AGC Chemicals Americas.Examples of polyisocyanates suitable for use in the B component include Desmodur A100A aliphatic polyisocyanate from Covestro, Desmodur N3200 aliphatic polyisocyanate from Covestro, Bayhydur 302 solvent-free water-dispersible aliphatic polyisocyanate from Covestro, and Drodur L75 aromatic polyisocyanate from DR Coats. Ink & Resins Pvt. Ltd. Several types of catalysts can be used to promote the reaction of the hydroxy groups on the polyol with the hydroxy groups on the isocyanate. A commonly used catalyst is dibutyltin dilaurate.
[0120] One-component (one-part) reactive urethanes can be formulated utilizing blocked isocyanates that dissociate at elevated temperatures for bake coating systems. Such one-component urethanes contain a polyol binder as well as the appropriate blocked isocyanate. Depending on the selection of polyol and blocked isocyanate, such coatings are used as primers and topcoats in automotive, coil coating, and product finishing applications. The blocked isocyanates can be aliphatic or aromatic, and there are a variety of blocking agents that react with isocyanate groups to form blocked isocyanates. Common blocking agents include caprolactone, methyl ethyl ketoxime, 1,3 pyrazole, diisopropanolamine, and 3,3 dimethylpyrazole. The unblocking temperature of the blocked isocyanates depends on the blocking agent used as well as the presence of a catalyst such as dibutyltin dilaurate. For example, caprolactone-blocked IPDI-trimethylol polyether triol is 163° C. with dibutyltin dilaurate catalyst, whereas 3,5-dimethylpyrazole-blocked IPDI-trimethylol polyether triol is 112° C. in the presence of dibutyltin dilaurate catalyst.
[0121] Suitable polymeric binder materials are selected from acrylics, vinyls, polyesters, siliconized polyesters, alkyds, polyurethanes, epoxies, phenolics, epoxy-phenolics, fluoropolymers, halopolymers (such as polyvinylidene fluoride, fluorinated ethylene vinyl ether [FEVE], polyvinyl chloride, polychloroprine, etc.), polybutadienes, polyolefins, hybrid polymers, polyether polyols, polysiloxanes, and any combination thereof. Other polymers may also be present, such as those incorporating monomers into polyvinyl acetate.
[0122] Other Ingredients The composition may include particulate materials. Typically, the particulate materials improve the color, opacity and / or mechanical robustness of the composition. Materials can be used in combination to provide the specific properties required.
[0123] Particulate materials include pigments, auxiliary pigments (also known as extenders), matting agents, fillers, ceramic beads, glitter beads, hollow glass beads, plastic beads, and any combination thereof.
[0124] Many particulate materials have multiple functions: for example, synthetic aluminosilicate "extender" particulate materials can improve pigment efficacy (thus reducing the amount required), change (e.g., increase) the opacity of the coating composition, and / or provide improved abrasion resistance.
[0125] The filler particulates and / or auxiliary pigments can be added to the coating composition at relatively high levels. The total amount of filler particulates and auxiliary pigments present in the composition can be 1 wt% or more, or 10 wt% or more, and up to 40 wt%.
[0126] Suitable particulate materials include calcium carbonate, calcium sulfate, calcium silicate, gypsum, barium sulfate, dolomite, mica, kaolin (which may be calcined kaolin), talc, nepheline syenate, quartz, feldspar, diatomaceous earth, aluminosilicates, aluminum oxide, wollastonite, precipitated barium sulfate (blanc fixe), barium sulfate, lithophon, corrosion-inhibiting pigments such as those available from ICI, e.g., ICI's HALOX SZP-391, zinc phosphate (which may inhibit corrosion due to its ability to quell corrosion at the anode or cathode of an electrochemical corrosion process), and any combination thereof.
[0127] Auxiliary Pigments Auxiliary pigments, also called extenders, can improve the efficacy of pigments as well as provide special performance attributes. For example, talc improves sanding properties, lithopone improves hardness in primer formulations, and mica reduces moisture penetration due to its plate-like structure. Auxiliary pigments are also typically fillers, and their cost is generally much lower than that of pigments. The composition may contain 1 wt% or more, alternatively 10 wt% or more, and up to 40 wt% of auxiliary pigments.
[0128] Filler Suitable fillers are typically filler particulates, which are typically low cost and are typically added at high levels to bulk up the volume of the coating composition and often also provide mechanical robustness. The composition may contain 1 wt% or more, or 10 wt% or more, and up to 40 wt% of filler particulate matter.
[0129] Pigments Suitable pigments are functional pigments. These functional pigments provide specific performance attributes such as mechanical properties, improved corrosion resistance, sandability, abrasion resistance, gloss control, improved resistance to atmospheric pollution, resistance to moisture penetration, etc. For example, precipitated barium sulfate (synthetic barium sulfate), barium sulfate, lithophon, fumed silica, corrosion-inhibiting pigments such as those available from ICL, e.g., halox SZP-391, zinc phosphate (which can inhibit corrosion due to its ability to quell corrosion at the anode or cathode of an electrochemical corrosion process).
[0130] Suitable pigments are color pigments.Suitable pigments include copper phthalocynanine, cobalt blue, Prussian blue (all of which typically provide blue colors); cobalt green, chromium oxide, phthalocyanine green (all of which typically provide green colors); quinacridone red, red iron oxide (all of which typically provide red colors); yellow iron oxide, cadmium yellow (all of which typically provide yellow colors); carbon black, black iron oxide (all of which typically provide black colors); ultramarine violet, quinacridone violet (all of which typically provide purple colors); and any combination thereof.
[0131] These pigments can be used for special visual effects or a combination of color and functionality, e.g. IR reflective pigments, and for aesthetic purposes. Suitable pigments can be organic, inorganic, ceramic, metallic, IR reflective, special effect or color.
[0132] Suitable pigments include, but are not limited to, copper phthalocyanine, green tea, cobalt blue, cobalt green, chromium oxide, phthalocyanine green, quinacridone red, red iron oxide (all of which typically provide red colors); yellow iron oxide, cadmium yellow, carbon black, black iron oxide, ultramarine violet, quinacridone violet (all of which typically provide purple colors); and any combination thereof. Examples of suppliers of inorganic pigments include Bayferrox, Ferro, Cathay Industries. Examples of suppliers of organic pigments include Clarient, Zeya Chemicals Co., Lansco. Examples of suppliers of ceramic pigments include Ferro, Shepherd Color Company. Examples of suppliers of IR reflective pigments or pigment dispersions include Eckart, Ferro, Chromaflo, Shepherd Color Company. Metallic pigments include, for example, those consisting essentially of aluminum, zinc, copper, nickel, and stainless steel particles. Examples of suppliers of metallic pigments include Silberline and Eckart. Special effect pigments provide appearance characteristics that may include iridescence, sparkle, different colors, or other special effects depending on the viewer's viewing angle. Examples of special effect pigment suppliers include CQV, Eckart, and EMD.
[0133] Suitable pigments include inorganic color pigments such as zinc white, pigment grade zinc oxide; zinc sulfide, lithopone black pigments such as black iron oxide (CI Pigment Black 11), iron manganese black, spinel black (CI Pigment Black 27); carbon black (CI Pigment Black 7); and chromatic pigments such as chromium oxide, chromium oxide hydrate green; chrome green (CI Pigment Green 48); cobalt green (CI Pigment Green 50); ultramarine green; cobalt blue (CI Pigment Blue 28 and 36; CI Pigment Blue 72); ultramarine blue; manganese blue; ultramarine violet; cobalt violet; manganese violet; red iron oxide (CI Pigment Red 101); cadmium sulfide selenide (CI Pigment Red 108); cerium sulfide (CI Pigment Red 265); molybdate red (CI Pigment Red 104);Ultramarine Red;Brown Iron Oxide (CI Pigment Brown 6 and 7), Mixed Brown, Spinel and Corundum Phases (CI Pigment Brown 29, 31, 33, 34, 35, 37, 39, and 40);Chrome Titanium Yellow (CI Pigment Brown 24);Chrome Orange;Cerium Sulfide (CI Pigment Orange 75),Yellow Iron Oxide (CI Pigment Yellow 42),Nickel Titanium Yellow (CI Pigment Yellow 53; CI Pigment Yellow 157, 158, 159, 160, 161, 162, 163, 164, and 189);Spinel Phase (CI Pigment Yellow 119);Cadmium Sulfide and Cadmium Zinc Sulfide (CI Pigment Yellow 37 and 35);Chrome Yellow (CI Pigment Yellow 34); Bismuth vanadate (CIPigment Yellow 184), and any combination thereof.
[0134] Suitable pigments include organic color pigments, such as monoazo pigments, e.g., CI Pigment Brown 25; CI Pigment Orange 5, 13, 36, 38, 64, 67, and 74; CI Pigment Red 1, 2, 3, 4, 5, 8, 9, 12, 17, 22, 23, 31, 48:1, 48:2, 48:3, 48:4, 49, 49:1, 51:1, 52:1, 52:2, 53, 53:1, 53:3, 57:1, 58:2, 58:4, 63, 112, 146, 148, 170, 175, 184, 185, 187, 191:1, 208, 210, 245, 247, and 251;CI Pigment Yellow 1, 3, 62, 65, 73, 74, 97, 120, 151, 154, 168, 181, 183, and 191;CI Pigment Violet 32;diazo pigments, such as CI Pigment Orange 16, 34, 44, and 72;CI Pigment Yellow 12, 13, 14, 16, 17, 81, 83, 106, 113, 126, 127, 155, 170, 174, 176, 180, and 188;diazo condensation pigments, such as CI Pigment Yellow 93, 95, and 128;CI Pigment Red 144, 166, 214, 220, 221, 242, and 262;CI Pigment Brown 23 and 41;anthanthrone pigments, such as CI Pigment Red 168;anthraquinone pigments, such as CI Pigment Yellow 147, 177, and 199;CI Pigment Violet 31;anthrapyrimidine pigments, such as CI Pigment Yellow 108;quinacridone pigments, such as Pigment Orange 48 and 49;CI Pigment Red 122, 202, 206 and 209;CI Pigment Violet 19;quinophthalone pigments, such as CIPigment Yellow 138; diketopyrrolopyrrole pigments, such as CI Pigment Orange 71, 73, and 81; CI Pigment Red 254, 255, 264, 270, and 272; dioxazine pigments, such as CI Pigment Violet 23 and 37; CI Pigment Blue 80; flavanthrone pigments, such as CI Pigment Yellow 24; indanthrone pigments, such as CI Pigment Blue 60 and 64; isoindoline pigments, such as CI Pigments Orange 61 and 69; CI Pigment Red 260; CI Pigment Yellow 139 and 185; isoindolinone pigments, such as CI Pigment Yellow 109, 110, and 173; isoviolanthrone pigments, such as CI Pigment Violet 31; metal complex pigments, such as CI Pigment Red 257; CI Pigment Yellow 117, 129, 150, 153, and 177; CI Pigment Green 8; perinone pigments, such as CI Pigment Orange 43; CI Pigment Red 194; perylene pigments, such as CI Pigment Black 31 and 32; CI Pigment Red 123, 149, 178, 179, 190, and 224; CI Pigment Violet 29; phthalocyanine pigments, such as CI Pigment Blue 15, 15:1, 15:2, 15:3, 15:4, 15:6, and 16; CI Pigment Green 7 and 36; pyranthrone pigments, such as CI Pigment Orange 51; CI Pigment Red 216; pyrazoloquinazolone pigments, such as CI Pigment Orange 67; CI Pigment Red 251; thioindigo pigments, such as CIPigment Red 88 and 181;CI Pigment Violet 38;triarylcarbonium pigments such as CI Pigment Blue 1, 61, and 62;CI Pigment Green 1;CI Pigment Red 81, 81:1, and 169;CI Pigment Violet 1, 2, 3, and 27;CI Pigment Black 1 (Aniline Black);CI Pigment Yellow 101 (Aldazine Yellow);CI Pigment Brown 22;and any combination thereof.
[0135] Coalescent agent A flocculant is a substance that promotes the coalescence of polymer particles during the drying and film-forming process. The flocculant is usually a liquid. Typically, the flocculant softens and plasticizes the outer surface of the polymer particles, allowing the polymer particles to coalesce, which leads to film formation. Suitable flocculants include ester alcohols, esters, glycol ethers, and any combination thereof.
[0136] Rheology modifier Rheology modifiers are ingredients that change (usually thicken) the rheological profile of a coating composition.
[0137] Suitable rheology modifiers are thickeners. Preferred thickeners are associative thickeners. For aqueous based compositions, particularly preferred thickeners are associative thickeners.
[0138] Suitable thickeners include hydrophobically modified alkali soluble emulsions, typically called HASE (hydrophobically modified alkali soluble emulsion); alkali soluble emulsions, typically called ASE (alkali soluble emulsion); hydrophobically modified ethylene oxide-urethane emulsions, typically called HEUR (hydrophobically modified ethylene oxide-urethane emulsion); hydrophobically modified ethoxylated urethane alkali swellable emulsions, typically called HEURASE (hydrophobically modified ethoxylated urethane alkali swellable emulsion); cellulosic thickeners, such as hydroxymethylcellulose, hydroxyethylcellulose, 2-hydroxyethylmethylcellulose, 2-hydroxybutylmethylcellulose, hydrophobically modified hydroxyethylcellulose, sodium carboxymethylcellulose, sodium carboxymethyl 2-hydroxyethylcellulose, 2-hydroxypropylmethylcellulose, 2-hydroxyethylethylcellulose, 2-hydroxypropylcellulose, typically HMEC (hydrophobically modified ethyl cellulose). hydrophobically modified ethyl cellulose, also known as cellulose, and any combination thereof; polyvinyl alcohol (PVA); fumed silica; bentonite clay; and any combination thereof. These thickeners are particularly suited for aqueous based compositions.
[0139] Suitable rheology modifiers are the Dow Acrysol line of products, Arkema Coatex Coapur, Rheotech, Viscoatex, Thixol and Polyphobe line of products, Ashland Chemical Aquaflow NSAT line of products (particularly Aquaflow NHS-310), and any combinations thereof. Another suitable rheology modifier is Natrosol HEC. Common rheology modifiers in solvent-based coating compositions include organo-clays, hydrogenated castor wax, polyamides, fumed silica, and any combination thereof.
[0140] Neutralizer Most water-based carboxylate polymers require an amine-based neutralizing agent. The neutralizing agent increases the polarity (strength of positive-negative charge) when added to the water-based polymer, resulting in improved water dispersibility and allowing incorporation into water-based systems. Typical examples of amine-based neutralizing agents used for water-based polymers in coatings include ammonium hydroxide, triethylaminomethylpropanol, and dimethylethanolamine.
[0141] Wetting agents / dispersants Dispersants Dispersants are used to facilitate the process of incorporating insoluble solids (like pigments), helping to suspend the solid particles in the liquid and stabilizing them against flocculation and settling. Dispersants can also reduce the particle size of solid particles in the liquid, stabilizing them against flocculation and settling. Suitable dispersants include surfactants, which can act to wet the pigment particles (displacing water and air on the surface of the pigment) and stabilize the pigment particles from recombining to form larger agglomerated particles.
[0142] Suitable dispersants include nonionic, anionic and cationic dispersants. Cationic dispersants include 2-amino 2-methyl 1-propanol (AMP) and dimethylaminoethanol (DMAE). Other suitable dispersing agents include potassium tripolyphosphate (KTPP), trisodium polyphosphate, citric acid and other carboxylic acids, and any combination thereof. The surfactant may also function as a dispersant.
[0143] Dispersants are typically added at very low levels, such as less than 1.0 wt%, or less than 0.5 wt%, or less than 0.2 wt% of the coating composition. A suitable dispersant is Dow's Tamol 165A. Other suitable dispersants include Tamol 731A, Tamol 1124, Coatex Coadis 123K, and combinations thereof. Suitable dispersants are available from Arkema, Byk, BASF, Buckman and Patchem.
[0144] Wetting Agent Wetting agents are surface active substances used to reduce the surface tension of water, making it easier to incorporate into water. Wetting agents can also be used to reduce the surface tension of dissimilar materials in a paint formulation, making them easier to incorporate or mix. Wetting agents, like surfactants, can be anionic, cationic or non-ionic. Suitable wetting agents are available from Croda.
[0145] An example of a wetting agent is polyvinyl butyral, which depending on the molecular weight and level of acetalization can be used as a wetting agent.
[0146] Surfactants Surfactants are used as wetting agents and dispersing agents. Surfactants may be anionic, nonionic or cationic. An example of a nonionic surfactant used as a wetting agent is Hydropalat WE 3320 from BASF.
[0147] Flow and levelling agent Flow and leveling agents improve flow and leveling as well as substrate wetting and reduce surface defects such as fish eyes, craters, orange peel, trapped air release, etc. Suitable flow and leveling agents are available from Allnex, Estron, and Patchem.
[0148] Dryer Dryers are catalysts commonly added to oil-based paint compositions to promote crosslinking of the oil. Suitable driers include iron octoate, calcium octoate, cobalt octoate, zinc octoate, copper octoate, barium octoate, lead octoate, red lead, litharge, and any combination thereof.
[0149] Defoamer Defoamers are typically added to coating compositions to control (e.g., reduce) the formation of foam, which can become entrained with air during manufacture and application, leading to a variety of adverse consequences.
[0150] In water-based coating compositions, defoamers are primarily used to avoid air entrapment during manufacturing and packaging due to the presence of surfactants and other surface-active substances commonly present in water-based coating compositions. In solvent-based coating compositions, defoamers are used primarily to prevent air entrapment during application.
[0151] Suitable defoamers are silicone-based emulsions such as polysiloxanes (e.g., polydimethylsiloxane [PDMS]). Other suitable defoamers are other hydrophobically modified polymers, mineral oils, fatty acids, and any combination thereof.
[0152] A suitable defoamer is BASF's Foamstar ST-2420, which is a branched polymer-based defoamer. Another suitable defoamer is BASF's Foamstar SI 2250, which is a silicone-based defoamer. Suitable suppliers of antifoam agents include Estron, Dynea, and BASF. Defoamers are also known as air release agents.
[0153] Antifreeze agent To avoid instability in cold weather (e.g., due to freeze-thaw cycles), it may be necessary to add an antifreeze to the paint emulsion. Suitable antifreezes include glycols, such as monopropylene glycol. Another suitable antifreeze is a nonionic surfactant, which can also improve the stability of the product under cold conditions. Antifreezes, such as nonionic surfactants, often provide multiple functionalities.
[0154] Freeze / thaw preventative The composition may include a freeze / thaw protection agent. Suitable freeze / thaw protection agents include propylene glycol, DpnB, rotoline FT 100E, and any combination thereof.
[0155] Biocides and mildewcides If the coating composition needs to be resistant to mold, especially mildew, a biocide, especially a mildew inhibitor, can be incorporated into the coating composition.Suitable mildew inhibitors include zinc oxide, isothiazolones, triazoles, and any combination thereof.Suitable isothiazolones include 2-octyl-3-isothiazolone, 4,5-dichloro-2-octyl-3-isothiazolone, 5-chloro-2-(2-4(chlorophenyl)ethyl)-3-isothiazolone, 5-chloro-2-(2-phenylethyl)-3-isothiazolone, and any combination thereof.
[0156] Biocides can also be incorporated into the coating composition to improve in-can biostability and / or to act as antifouling agents after the coating composition is applied to the surface to be coated. Suitable biocides include isothiazolones, zinc pyrithione, chlorothalonil, silver nanoparticles, and any combination thereof.
[0157] There can be several strategies to control microbial contamination in coating compositions, including pH control. The levels of biocides, such as fungicides and mildewcides, added to coating compositions are very low, typically less than 0.1 wt%.
[0158] Crosslinking Agent Some coating compositions may include a crosslinking agent, which is particularly preferred when the composition includes a polyester.
[0159] Suitable crosslinkers are aminoplasts. Aminoplast crosslinkers typically have three or more reactive groups that react with hydroxy groups. Suitable crosslinkers include, but are not limited to, aminoplasts and isocyanate crosslinkers. Examples of suitable crosslinkers include aminoplast crosslinkers such as melamine formaldehyde, urea formaldehyde, and benzoguanamine. Typically, the polyester:aminoplast ratio is 10% to 30% by weight solids. Fully alkylated melamines such as hexamethoxymethylol melamine are typically preferred. Particularly suitable aminoplast crosslinkers include those from suppliers such as Allnex, including, but not limited to, melamine crosslinkers such as Cymel 303 LF, Cymel 300, Cymel 301, and Cymel 373.
[0160] One-component reactive urethanes can be formulated utilizing blocked isocyanates that dissociate at elevated temperatures for bake-on coating systems. Such one-component urethanes include a polyol binder as well as the appropriate blocked isocyanate. The blocked isocyanate can be aliphatic or aromatic, and there are a variety of blocking agents that react with isocyanate groups to form blocked isocyanates. Common blocking agents include caprolactone, methyl ethyl ketoxime, 1,3 pyrazole, diisopropanolamine, and 3,3 dimethylpyrazole. The unblocking temperature of the blocked isocyanates depends on the blocking agent used as well as the presence of a catalyst such as dibutyltin dilaurate. For example, caprolactone-blocked IPDI-trimethylol polyether triol is 163°C with dibutyltin dilaurate catalyst, whereas 3,5-dimethylpyrazole-blocked IPDI-trimethylol polyether triol is 112°C in the presence of dibutyltin dilaurate catalyst.
[0161] Also preferred are blocked aliphatic polyisocyanates, such as the isocyanurates of isophorone diisocyanate or hexamethylene diisocyanate blocked with diethyl maleate, dimethylpyrazole, or methyl ethyl ketoxime. Aliphatic blocked polyisocyanates are preferred over aromatic types for exterior topcoat applications, since aliphatic or cycloaliphatic blocked polyisocyanates have better UV light stability than aromatic blocked polyisocyanates. Mixtures of crosslinkers can also be used. Examples of blocked aliphatic polyisocyanates that are particularly suitable for this application include, but are not limited to, those manufactured by Baxenden Chemicals and Covestro, such as Desmodur BL 3175A, BL 3475BA / SN, PL 340, etc.
[0162] The composition may also include a catalyst to accelerate the rate of cure, which is generally added in an amount of about 0.2 to about 2.0 wt %, based on the weight of the binder solids.
[0163] For example, when aminoplast crosslinkers such as fully alkylated melamines are used, acid catalysts are used. Strong acid catalysts are preferred to enhance the cure rate. Such catalysts are well known in the art and include, but are not limited to, p-toluenesulfonic acid, methanesulfonic acid, nonylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, dodecylbenzenesulfonic acid, phenyl acid phosphate, monoalkyl and dialkyl acid phosphates, and the like. To enhance the stability of the package, the acid catalyst may be blocked, typically by forming an acid salt with an amine. Other catalysts useful for this application include Lewis acids, zinc salts, and tin salts. When an isocyanate crosslinker is used to form polyurethane bonds with pendant hydroxyl groups on the polyester, tin catalysts such as dibutyltin diacetate, dibutyltin dilaurate, and dibutyltin oxide can be used. Cobalt, zinc, and iron compounds may also be included with the tin catalyst to enhance cure.
[0164] Preferably, the composition may include from 0.1 wt% to 5.0 wt%, or from 0.2 wt% to 1.0 wt% of the catalyst. Preferably, the composition comprises 20wt% to 60wt%, or 30wt% to 40wt% of the hydroxy-functional polyester polymer and 5wt% to 20wt%, or 10wt% to 15wt% of the crosslinking agent.
[0165] The crosslinking agent typically reacts with the polymeric binder material to form a crosslinked polymeric binder material. A suitable crosslinker for polyester binder materials is triglycidyl isocyanurate (TGIC). The crosslinked polymeric binder material may be an epoxy ester. Depending on the stoichiometry and reaction conditions, one to three of the oxirane groups may theoretically react.
[0166] Carboxyl-functional polyesters can also be crosslinked with hydroxyl-functional hardeners such as β-hydroxyalkylamides. The crosslinking condensation reaction forms amide-ester heterocycles that liberate water. Polymeric blocked isocyanates are also suitable curing agents, especially in the powder coating industry. They are often used to crosslink acrylic and polyester powder resins that contain hydroxyl groups. This crosslinking forms urethane bonds, which, after liberation of the blocking agent, form polyurethanes.
[0167] Another common crosslinking agent for hydroxyl-functional polyesters is Powderlink® [登録商標] The preferred cross-linking material is tetramethoxymethyl glycoluril (TMMGU), also known as 1174. An ideal cross-linking material would form ether bonds after methanol is liberated.
[0168] Method for producing coating composition Coating compositions are usually manufactured in a two-stage process. First, the solvent, and optionally other liquid ingredients, are combined with the particulate material (such as pigments), and optionally some additives (such as dispersants, defoamers, and / or wetting agents) to form a blend. This blend is then milled to properly disperse the particulate matter, such as pigments, and / or to reduce the particle size of the particulate matter to the required size. Precise control of particle size is very important for the correct optical properties of the coating composition. This stage is called the "grind" stage. Fly ash is usually introduced in the grind stage to ensure dispersion.
[0169] After the grind is prepared, it is typically blended with a polymeric binder material and, optionally, other additives, which is commonly referred to as the "let down" step. Polymeric binder materials are usually added at the letdown stage. Flocculants and biocides are also usually added at the letdown stage.
[0170] Typically, solvents, rheology modifiers, neutralizing agents, wetting and dispersing agents, biocides, defoamers, antifreeze agents, TiO2 and other pigments, fly ash, and extenders are all added at the grind stage. Typically, polymeric binder materials, defoamers, neutralizing agents, solvents, rheology modifiers, mold inhibitors, etc. are added during the letdown stage.
[0171] Application of coating composition The coating composition can be used as a white coating. It is also possible to use the coating composition as a white base to which pigments and / or colorants are added, for example at the point of sale, for example at an in-store paint dispenser. These white base coatings are usually known as high white, medium white, and low white.
[0172] A typical application of the coating composition is for water-based architectural coatings, however, it can also be used for a wide variety of coating applications including water-based traffic markings, powder coatings, and solvent-based industrial and maintenance coatings.
[0173] Other applications include: architecture, aerospace, commercial, building products, transportation, product finishes, metal decorative, traffic signage, packaging and industrial, interior / exterior water-based topcoats and undercoats, primers for plastics, drywall, masonry, concrete, wood, metal, and asphalt roads.
[0174] Examples of application methods used in the paint industry include brush; roller; airless or air spray; plasma; direct or reverse roll coat; sheet coat; electrodeposition; electrostatic spray; electrostatic disk; spin coat; and dip coat.
[0175] architectural paint The coating composition is suitable for architectural coatings.
[0176] A highly preferred embodiment of the present invention comprises a white paint composition comprising: (a) 3wt%-35wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 50 wt% of a solvent; and (d) 10 wt % to 30 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0177] Another highly preferred embodiment of the present invention comprises a coating composition comprising: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% of a solvent; and (d) 10 wt % to 35 wt % of a polymeric binder material selected from modified or unmodified polyacrylates; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0178] Another highly preferred embodiment of the present invention comprises a coating composition, which is an aqueous based composition and comprises: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% water, and (d) 10 wt % to 35 wt % of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0179] Suitable polymeric binder materials are based on an acrylic monomer backbone. In a preferred polymeric binder material, the acrylic monomer is butyl-acrylate. Additional monomers may also be present for lower cost based on vinyl acetate monomer, or to improve performance using other acrylic monomers such as ethyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, and many others. Ethylene-vinyl acetate copolymer systems are also suitable.
[0180] Another suitable polymeric binder material is based on a styrene-acrylic monomer backbone.
[0181] Coil Coating The coating composition may be suitable for coil coating. A suitable coating composition is a solvent-based composition comprising: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 60 wt% TiO2 or other pigment; (c) 1.0 wt% to 70 wt% organic solvent; (d) 15 wt% to 80 wt% of a polymeric binder material; and (e) 3.0 wt % to 20 wt % of a crosslinker; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0182] The composition is typically a white or pastel paint. Preferably, the composition is an organic solvent-based paint composition. Preferably, the composition comprises 30 wt % to 60 wt % of the organic solvent. Typically, the composition has a viscosity in the range of 0.17 Pa·s to 0.40 Pa·s.
[0183] The viscosity of the coating composition can be adjusted as needed, for example, for storage stability and / or to accommodate various coil coating application methods (reverse application methods such as reverse roll coat, direct roll coat, extrusion, or cloud chamber, etc.).
[0184] The composition may include other powder materials. The composition may include from greater than 0 wt% to less than 30 wt%, or from 1.0 wt% to 27 wt%, or from 1.0 wt% to 25 wt%, or from 1.0 wt% to 20 wt%, or from 1.0 wt% to 15 wt% of other powder materials.
[0185] Suitable powder materials include materials for adjusting the optical or rheological properties of the composition, as well as additional pigments for providing color and / or metallic luster.
[0186] Other powder, bead and / or platelet-like materials may also be used to enhance color options, control gloss, performance properties or aesthetics, including silica, ceramic pigments or beads, polyester beads, polyamide, glass beads, mica, aluminum flakes, special effect pigments, and vesiculated beads.
[0187] Other powdered materials are used to provide functional properties or to reduce cost and include barium sulfate, talc, calcium carbonate, lithopone, clay, calcium sulfate, silica, quartz, mica, and any combination thereof. Other suitable powdered materials include calcium silicate and / or dolomite.
[0188] Other powder materials are used to enhance corrosion resistance when used in primers or as single layer topcoats. Such pigments inhibit corrosion by releasing low levels of soluble ions, inhibiting corrosion at the anode or cathode of the corrosion process. Examples include zinc phosphate, strontium chromate, and zinc chromate.
[0189] The paint may be brilliant white, but may also be off-white, such as a pastel color. Usually, the paint is the L of the paint (preferably the dried paint). * a * b * is defined by the value, where L * is greater than 80, a * and b * are independently within the range of ±10.
[0190] Typically, the composition has a whiteness L value of greater than 80, or greater than 85, or greater than 90, or greater than 95. Typically, the composition is white and the a and b values are each independently within the range of -10.0 to +10.0.
[0191] Because most coil coatings are applied at smaller film thicknesses than other coatings (such as those used in architecture, traffic signage, and industrial applications), white and pastel coil topcoat colors are often applied over a light-colored primer (e.g., light green or off-white) to ensure uniform color with low tolerance levels. This is especially preferred for applications such as building siding and appliances.
[0192] The composition typically includes other ingredients. Any suitable ingredients can be included in the composition. Suitable ingredients in addition to titanium dioxide and fly ash are described in more detail below.
[0193] The composition includes one or more organic solvents. The composition includes 10 wt % to 60 wt %, or 20 wt % to 50 wt % of an organic solvent.
[0194] Suitable solvents for solvent-based coil coatings depend on the binder and crosslinker selected. Polyester-based coil coatings, which represent the single largest coating type utilized in the industry, are referenced herein for purposes of illustration, however, other suitable coatings include acrylics, fluoropolymers, halogenated polymers, silicone polyesters, epoxies, epoxy esters, polyvinyl chlorides, and the like. Solvents commonly used in coil coatings include: oxygen-containing solvents (e.g., alcohols, ketones, esters, ethers, glycols, glycol ethers, glycol ether esters, ether esters, and the like), such as butanol, isobutanol, isopropanol, butyl cellosolve, PM acetate, diacetone alcohol, and the like, and hydrocarbons, such as, but not limited to, aromatic 100, aromatic 150, aromatic 200, VM&P naptha, xylene, toluene, and the like.
[0195] The solvent not only solubilizes the polymeric binder material, but also helps to adjust viscosity, minimize coating defects, provide flow and leveling, or the solvent can act as a liquid carrier material in which the polymeric binder does not dissolve, but instead forms a stable dispersion of the polymeric binder in the solvent.
[0196] The composition may contain a mixture of small amounts of water and a solvent such as an oxygenated hydrocarbon, In this mixed solvent system, the composition may contain from 1 wt% to about 10 wt% water.
[0197] In contrast to many other coating types, most coil coating lines incinerate the solvent to prevent it from entering the atmosphere, so there is little environmental risk. Solvents may also be exempt. Examples of exempt solvents include acetone, dimethyl carbonate, methyl acetate, parachlorobenzotrifluoride, tert-butyl acetate, propylene carbonate, and combinations thereof. Such exempt solvents may be used at higher levels than non-exempt solvents.
[0198] The composition may comprise from 10 wt% to 60 wt% of an organic solvent.The composition may comprise from 20 wt% to 60 wt% of an aliphatic and / or aromatic hydrocarbon. Preferably, the composition comprises from 10 wt% to 50 wt%, or from 20 wt% to 40 wt% of the polymeric binder material.
[0199] Preferably, the polymeric binder material is a hydroxy-functional saturated polyester resin, which may contain aromatic, aliphatic or cycloaliphatic components suitable for coil coatings. Such polyester resins are used with crosslinkers and are designed to crosslink when exposed to peak paint + metal substrate metal temperatures ranging from about 400 to 450 F for about 15 to 45 seconds at line speeds of up to about 700 feet per minute. Such coatings provide a good balance of desirable properties, including hardness, scratch or abrasion resistance, flexibility, chemical resistance, and resistance to degradation from external exposure.
[0200] The composition may include from 10 wt% to 60 wt%, or from 20 wt% to 40 wt% of the polyester polymer. Suitable polymeric binder materials are supplied by Polynt Composites, Allnex and DSM.
[0201] Particularly preferred polymeric binder materials are hydroxy-functional linear or branched polyesters that are synthesized with a molar excess of hydroxy functionality for reaction with aminoplasts and / or blocked or activated isocyanate crosslinkers and are used in one- or two-component coatings. Typically, for coil coating applications, one-component formulations are more preferred due to pot life issues associated with the use of isocyanate crosslinkers. Suitable hydroxy-functional polyester polymers are composed of one or more diols, which may include one or more triols, such as neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 1,6-hexanediol, ethylene or propylene glycol, 2,2,4-trimethyl-1,3-pentanediol, and 1,4-cyclohexanedimethanol, and trimethylolpropane, and suitable acid or anhydride functional monomers, typically suitable carboxyl functional aliphatic, alicyclic or aromatic acids containing two or more carboxyl functional acid groups, such as adipic acid, azelaic acid, sebacic acid, cyclohexanedicarboxylic acid, isophthalic acid, phthalic acid, terephthalic acid, hexahydrophthalic anhydride, trimellitic anhydride, and the like.
[0202] Suitable hydroxy-functional polyester polymers include the use of one or more of the hydroxy- and / or carboxy-functional building blocks listed above. Polyester resins are generally formed by step-growth polymerization of one or more alcohols having at least two hydroxy groups with a carboxylic acid having at least two carboxyl groups. Other routes to polyester synthesis include reaction of esters with alcohols, reaction of anhydrides with alcohols, ring-opening polymerization of lactones, and the like. Polyesters can also be modified with reactants such as benzoic acid, monofunctional epoxy-functional reactants (e.g., glycidyl esters of versatic acid), and the like. Synthesis of polyester resins can be carried out under suitable conditions, such as temperatures of about 145 to about 260° C. A catalyst (such as dibutyltin oxide or other suitable catalyst) is typically used. The by-product is typically water, which is removed by simple distillation, vacuum distillation, or azeotropic distillation to drive the reaction to completion.
[0203] The essentially linear polyester preferably has a number average molecular weight in the range of about 4,000 to about 5,000 and a weight average molecular weight of about 5,200 to about 8,000, with a polydispersity of preferably about 1.2 to about 2.0. Suitable polyester polymers are available from a number of suppliers, examples of suitable hydroxy-functional polyester suppliers include, but are not limited to, Uralac SN844 S2G3-60 ND or Uralac SN831 S2G3-60 ND, Uralac SN804 S2-65 ND supplied by DSM, Polymac 220-1939, Polymac 66-6613 supplied by Polynt Composites, and Setal 16-1084 supplied by Allnex.
[0204] Preferably, the polymeric binder is a hydroxy-functional saturated polyester, preferably supplied in the form of a solution in a suitable oxygen-containing organic solvent or petroleum distillate. The polyester is typically supplied at a solids content of 40 wt% to 80 wt%, or 60 wt% to 75 wt%.
[0205] Suitable hydroxy-functional polyesters for use in formulated coating compositions provide good flexibility, good hardness, good adhesion, good chemical resistance, good abrasion resistance, good overbaking resistance, and good outdoor weatherability.
[0206] The coating formulation may also include a crosslinking agent. Aminoplast crosslinkers typically have three or more reactive groups that react with hydroxy groups. Suitable crosslinkers include, but are not limited to, aminoplasts and isocyanate crosslinkers. Examples of suitable crosslinkers include aminoplast crosslinkers such as melamine formaldehyde, urea formaldehyde, and benzoguanamine. Typically, the polyester:aminoplast ratio is 10% to 30% by weight solids. Fully alkylated melamines such as hexamethoxymethylol melamine are typically preferred. Particularly suitable aminoplast crosslinkers include those from suppliers such as Allnex, including, but not limited to, melamine crosslinkers such as Cymel 303 LF, Cymel 300, Cymel 301, and Cymel 373.
[0207] One-component (one-part) reactive urethanes can be formulated utilizing blocked isocyanates that dissociate at elevated temperatures for bake-on coating systems. Such one-component urethanes include a polyol binder as well as the appropriate blocked isocyanate. The blocked isocyanates can be aliphatic or aromatic, and there are a variety of blocking agents that react with isocyanate groups to form blocked isocyanates. Common blocking agents include caprolactone, methyl ethyl ketoxime, 1,3 pyrazole, diisopropanolamine, and 3,3 dimethylpyrazole. The unblocking temperature of the blocked isocyanates depends on the blocking agent used as well as the presence of a catalyst such as dibutyltin dilaurate. For example, caprolactone-blocked IPDI-trimethylol polyether triol is 163°C with dibutyltin dilaurate catalyst, whereas 3,5-dimethylpyrazole-blocked IPDI-trimethylol polyether triol is 112°C in the presence of dibutyltin dilaurate catalyst.
[0208] Also preferred are blocked aliphatic polyisocyanates, such as the isocyanurates of isophorone diisocyanate or hexamethylene diisocyanate blocked with diethyl maleate, dimethylpyrazole, or methyl ethyl ketoxime. Aliphatic blocked polyisocyanates are preferred over aromatic types for exterior topcoat applications, since aliphatic or cycloaliphatic blocked polyisocyanates have better UV light stability than aromatic blocked polyisocyanates. Mixtures of crosslinkers can also be used. Examples of blocked aliphatic polyisocyanates that are particularly suitable for this application include, but are not limited to, those manufactured by Baxenden Chemicals and Covestro, such as Desmodur BL 3175A, BL 3475BA / SN, PL 340, etc.
[0209] The coating composition may also include a catalyst to accelerate the rate of cure, which is generally added in an amount of about 0.2 to about 2.0 wt %, based on the weight of the binder solids.
[0210] For example, when aminoplast crosslinkers such as fully alkylated melamines are used, acid catalysts are used, with strong acid catalysts being preferred to enhance cure speed. Such catalysts are well known in the art and include, but are not limited to, p-toluenesulfonic acid, methanesulfonic acid, nonylbenzenesulfonic acid, dinonylnaphthalenedisulfonic acid, dinonylnaphthalenesulfonic acid, dodecylbenzenesulfonic acid, phenyl acid phosphate, monoalkyl and dialkyl acid phosphates, and the like. To enhance package stability, the acid catalyst may be blocked, typically with an amine to form an acid salt. Other catalysts useful for this application include Lewis acids, zinc salts, and tin salts. When isocyanate crosslinkers are used to form polyurethane bonds with pendant hydroxyl groups on polyesters, tin catalysts such as dibutyltin diacetate, dibutyltin dilaurate, and dibutyltin oxide can be used. Cobalt, zinc, and iron compounds may also be included with the tin catalyst to enhance cure.
[0211] Suitable polyester polymers are available from a number of suppliers, examples of suitable hydroxy-functional polyester suppliers include, but are not limited to, Uralac SN844 S2G3-60 ND or Uralac SN831 S2G3-60 ND, Uralac SN804 S2-65 ND supplied by DSM, Polymac 220-1939, Polymac 66-6613 supplied by Polynt Composites, and Setal 16-1084 supplied by Allnex.
[0212] Preferably, the polymeric binder is a hydroxy-functional saturated polyester, preferably supplied in the form of a solution in a suitable oxygen-containing organic solvent or petroleum distillate. The polyester is typically supplied at a solids content of 40 wt% to 80 wt%, or 60 wt% to 75 wt%.
[0213] Suitable hydroxy-functional polyesters for use in formulated coating compositions provide good flexibility, good hardness, good adhesion, good chemical resistance, good abrasion resistance, good overbaking resistance, and good outdoor weatherability.
[0214] Preferably, the composition comprises 20wt% to 60wt%, or 30wt% to 40wt% of the hydroxy-functional polyester polymer and 5wt% to 20wt%, or 10wt% to 15wt% of the crosslinking agent. Preferably, the catalyst or combination of catalysts comprises from 0.1 wt% to 5 wt%, or from 0.2 wt% to 1 wt%.
[0215] In addition to hydroxy-functional polyester resins, other suitable polymeric binder materials can also be used in coil coatings containing fly ash. Suitable polymeric binder materials also include silicon modified polyesters, such as siliconized polyesters (siliconized polyesters). Typically, such polyesters are also used in combination with organic solvents, typically aliphatic hydrocarbons, and oxygen-containing organic solvents. Other suitable polymeric binder materials are selected from the following: acrylics, modified acrylics, polysiloxanes; silane modified polymers; halopolymers, such as fluoropolymers (e.g., polyvinylidene fluoride, FEVE (fluorinated ethylene vinyl ether); polyvinyl chloride; polychloroprene, plastisols (PVC and plasticizers), inorganic polymer coating systems; phenolic resins (including epoxy-phenolic resins); polybutadienes, polyolefins, hybrid polymers, polyether polyols, and any combination thereof. Other polymers may also be present, such as polymers incorporating monomers into polyvinyl acetate.
[0216] Powder Coating The coating composition is suitable for powder coating. Suitable coating compositions include: (a) 10wt%-40wt% fly ash; (b) 1wt%–60wt% TiO2; (c) 15 wt% to 80 wt% of a polymeric binder material; and (d) 3.0 wt % to 20 wt % of a crosslinker; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0217] Powder coating compositions are typically solid compositions, which generally comprise a solid film-forming resin or a mixture of different types of resins, and usually contain one or more pigments (as described in the previous section), and optionally one or more performance additives such as plasticizers, stabilizers, flow aids, and extenders. The resins are usually thermosetting, incorporating, for example, a binder resin and a corresponding crosslinker (which may itself be a separate binder resin). Generally, the resins have a Tg, softening point, or melting point, greater than 30°C.
[0218] Traditionally, the manufacture of powder coatings involves melt mixing the components of the composition. Melt mixing involves mixing the dry components at high speed and intensity, then heating the mixture to a high temperature (above the softening temperature of the resin, but below the curing temperature) in a continuous compounder to form a molten mixture. The compounder preferably includes a single or twin screw extruder, as this serves to improve the dispersion of the other ingredients into the resin as it melts. The molten mixture is usually extruded, typically wound into a sheet, cooled to solidify the mixture, and then crushed into flakes, which are then ground into a fine powder.
[0219] Such processing is usually followed by a series of particle screening and separation operations (grinding, classification, sifting, screening, cyclonic separation, sieving, filtering, etc.) before the powder is applied to a substrate and heated to melt and fuse the particles and cure the coating. The main methods for applying powder coatings include the fluidized bed process, in which the substrate is preheated and immersed in a fluidized bed of powder, where the powder fuses and adheres to the substrate upon contact with the hot surface, and the electrostatic fluidized bed and electrostatic spray processes, in which the powder coating particles are electrostatically charged by an electrode in the fluidized bed or by an electrostatic spray gun and deposited on a grounded substrate.
[0220] The ultra-durable polyester powder coating composition can be described as follows: (i) a polyester resin A and a curing agent for the polyester resin; (ii) a polyester resin B and a curing agent for the polyester resin; (iii) Titanium dioxide (iv) a hydrophobic filler; and (v) Fly ash Here, polyester resin A and polyester resin B are not the same.
[0221] The powder coating compositions used in the various embodiments of the present invention may include a solid polymeric binder system comprising a carboxy-functional polyester film-forming resin. Such carboxy-functional polyester systems are currently the most widely used powder coating materials. The polyesters generally have an acid number in the range of 12 to 110, a number average molecular weight Mn of 1,500 to 10,000, and a glass transition temperature (Tg) of 30°C to 95°C, preferably at least 40°C. Suitable polyester resins can be prepared by reacting OH-functional monomers (e.g., glycol, neopentyl glycol, trimethylolpropane) with acid-functional monomers (e.g., terephthalic acid, isophthalic acid, phthalic acid). Preferably, at least one of the polyester resins A or B is an amorphous polyester resin. The other polyester resin may be amorphous or semi-crystalline.
[0222] Polyester resin A may have an acid value in the range of 33 to 75 mgKOH / g, and polyester resin B may have an acid value in the range of 15 to 48 mgKOH / g. Polyester resin A may have a softening point in the range of 40 to 75°C, and polyester resin B may have a softening point in the range of 28 to 51°C.
[0223] It is well known to use carboxy-functional polyester film-forming resins in combination with epoxy curing or crosslinking agents in powder coating compositions. Typically, triglycidyl isocyanurate is used as a crosslinking agent for carboxy-functional polyesters. However, a polyester powder coating composition may contain a curing agent for polyester resin A and a curing agent for polyester resin B that are substantially free of triglycidyl isocyanurate (TGIC). By substantially free, it is meant that the total composition contains less than 1.0 wt% TGIC (based on the total weight of the composition), preferably less than 0.5 wt%, and more preferably less than 0.1 wt%.
[0224] The use of hydroxyalkylamide compounds as curing agents can provide powder coating compositions with excellent durability and moisture resistance. Examples of suitable curing agents include bis(β-hydroxyalkylamide) curing agents such as tetrakis(2-hydroxyethyl)adipamide.
[0225] Alternatively, polyepoxy compounds that are solid at room temperature and contain at least two epoxy groups per molecule (such as diglycidyl terephthalate, triglycidyl trimellitate, or mixtures thereof) can also be used as curing agents.
[0226] In addition to the polyester film-forming resin, the hardener, and the fly ash, the powder coating composition according to the invention may also contain one or more pigments. Examples of pigments that may be used are inorganic pigments such as titanium dioxide, red and yellow iron oxides, chrome pigments, and carbon black, and organic pigments such as phthalocyanine, azo, anthraquinone, thioindigo, isodibenzanthrone, triphendioxane, and quinacridone pigments, vat dye pigments, and lakes of acid, basic, and mordant dyes. Dyes may be used in place of or as well as pigments.
[0227] A suitable composition is a polyester powder coating composition comprising: (i) 30 to 40 wt % of polyester resin A; (ii) 30 to 40 wt % of polyester resin B; (iii) 2 to 10 wt % of a hardener for polyester resin A and polyester resin B; (iv) 15 to 50 wt. % fly ash or a mixture of hydrophobic fillers and titanium dioxide; (v) pigments and fly ash; Here, wt % is calculated based on the total weight of the powder coating composition.
[0228] The compositions of the invention may also contain one or more performance additives, such as flow control agents, dispersants, plasticizers, stabilizers against UV degradation (antioxidants and / or UV absorbers), or degassing agents such as benzoin, or two or more such additives may be used. Typically, the coating compositions of the invention contain 0-5 wt% of one or more performance additives.
[0229] Like the pigment, these other additives can be included during or after the binder component is dispersed, but for optimum distribution it is preferred to mix them with the binder component before both are dispersed.
[0230] The powder coating composition of the present invention can be prepared by a process comprising the steps of: (i) preparing a polyester powder coating composition A comprising a polyester resin A and a curing agent for the polyester resin; and (ii) preparing a polyester powder coating composition B comprising a polyester resin B and a curing agent for said polyester resin; and dry mixing said polyester powder coating composition A and polyester powder coating composition B, wherein polyester resin A and polyester resin B are not identical, and polyester powder coating composition A and / or polyester powder coating composition B comprise a hydrophobic filler and / or fly ash.
[0231] In the conventional process for manufacturing powder coating compositions, all the components of the powder coating are premixed and then melt mixed in an extruder. The molten mixture is then cooled and granulated / milled to produce the powder coating.
[0232] The composition may be polyester powder coating composition A comprising polyester resin A and a curing agent for said polyester resin, prepared by melt mixing in an extruder as described above from a premix containing all the components of powder coating composition A. In a separate step, polyester powder coating composition B comprising polyester resin B and a curing agent for said polyester resin is also prepared by melt mixing in an extruder as described above from a premix containing all the components of powder coating composition B. Both powder coating compositions A and B are then dry mixed to obtain a powder coating composition according to the invention, with the proviso that either powder coating composition A or powder coating composition B, or both compositions, contain fly ash.
[0233] The powder coating composition according to the invention may in principle be applied to a substrate by any process of powder coating technology, for example by electrostatic spray coating (corona charging or tribo-charging) or by a fluidized bed process or an electrostatic fluidized bed process.
[0234] After the powder coating composition has been applied to a substrate, the conversion of the resulting deposited particles into a continuous coating (including, where appropriate, the curing of the applied composition) can be carried out by heat treatment and / or by radiant energy, in particular infrared, ultraviolet or electron beam radiation. The powder is usually cured on the substrate by application of heat (stoving process); the powder particles melt and flow, forming a film. The curing time and temperature are interdependent depending on the formulation of the composition used. The substrate may comprise metal, heat stable plastic material, wood, glass, or ceramic or textile material. Advantageously, metallic substrates are chemically or mechanically cleaned before application of the composition, and preferably chemically pretreated, for example with iron phosphate, zinc phosphate or chromate. Substrates other than metal are generally preheated before application or, in the case of electrostatic spray application, pretreated with a material that aids such application.
[0235] [Table 1]
[0236] The ultra-durable polyester powder coating composition can be described as follows: 1. A powder coating composition comprising: (i) a polyester resin A and a curing agent for the polyester resin; (ii) a polyester resin B and a curing agent for the polyester resin; (iii) Titanium dioxide and content; (iv) a hydrophobic filler; and (v) Fly ash Including, Here, polyester resin A and polyester resin B are not the same.
[0237] The powder coating compositions used in various embodiments of the present invention comprise a solid polymeric binder system comprising a carboxy-functional polyester film-forming resin. Such carboxy-functional polyester systems are currently the most widely used powder coating materials. The polyesters generally have an acid number in the range of 12 to 110, a number average molecular weight Mn of 1,500 to 10,000, and a glass transition temperature (Tg) of 30°C to 95°C, preferably at least 40°C. Suitable polyester resins can be prepared by reacting OH-functional monomers (e.g., glycol, neopentyl glycol, trimethylolpropane) with acid-functional monomers (e.g., terephthalic acid, isophthalic acid, phthalic acid). At least one of the polyester resins A or B is desirably an amorphous polyester resin. The other polyester resin may be amorphous or semi-crystalline.
[0238] The composition may be a polyester powder coating composition, where polyester resin A has an acid number in the range of 33 to 75 mgKOH / g and polyester resin B has an acid number in the range of 15 to 48 mgKOH / g. The composition may be a polyester powder coating composition, where polyester resin A has a softening point Tg in the range of 40-75°C and polyester resin B has a softening point Tg in the range of 28-51°C.
[0239] In addition to the polyester film-forming resin, the hardener, and the fly ash, the powder coating composition according to the invention may also contain one or more pigments. Examples of pigments that may be used are inorganic pigments such as titanium dioxide, red and yellow iron oxides, chrome pigments, and carbon black, and organic pigments such as phthalocyanine, azo, anthraquinone, thioindigo, isodibenzanthrone, triphendioxane, and quinacridone pigments, vat dye pigments, and lakes of acid, basic, and mordant dyes. Dyes may be used in place of or as well as pigments.
[0240] The composition may be a polyester powder coating composition comprising: (i) 30-40 wt % polyester resin A; (ii) 30-40 wt % polyester resin B; (iii) 2 to 10 wt % of a hardener for polyester resin A and polyester resin B; (iv) 10-40 wt% fly ash or a mixture of hydrophobic filler and fly ash; (v) 5 to 25 wt. % TiO2 and pigment; and (iv) 5 to 25 wt % hydrophobic filler Here, wt % is calculated based on the total weight of the powder coating composition.
[0241] The compositions of the invention may also contain one or more performance additives, such as flow control agents, dispersants, plasticizers, stabilizers against UV degradation (antioxidants and / or UV absorbers), or degassing agents, such as benzoin, or two or more such additives may be used. Typically, the coating compositions of the invention contain 0-5 wt % of one or more performance additives.
[0242] Like the pigment, these other additives can be included during or after the binder component is dispersed, but for optimum distribution it is preferred to mix them with the binder component before both are dispersed.
[0243] The powder coating composition of the present invention can be prepared by a process comprising the steps of: (i) preparing a polyester powder coating composition A comprising a polyester resin A and a curing agent for the polyester resin; and (ii) preparing a polyester powder coating composition B comprising a polyester resin B and a curing agent for said polyester resin; and dry mixing said polyester powder coating composition A and polyester powder coating composition B, wherein polyester resin A and polyester resin B are not identical, and polyester powder coating composition A and / or polyester powder coating composition B comprise a hydrophobic filler and / or fly ash.
[0244] In the conventional process for manufacturing powder coating compositions, all the components of the powder coating are premixed and then melt mixed in an extruder. The molten mixture is then cooled and granulated / milled to produce the powder coating.
[0245] The composition may be polyester powder coating composition A comprising polyester resin A and a curing agent for said polyester resin, prepared by melt mixing in an extruder as described above from a premix containing all the components of powder coating composition A. In a separate step, polyester powder coating composition B comprising polyester resin B and a curing agent for said polyester resin is also prepared by melt mixing in an extruder as described above from a premix containing all the components of powder coating composition B. Both powder coating compositions A and B are then dry mixed to obtain a powder coating composition according to the invention, with the proviso that either powder coating composition A or powder coating composition B, or both compositions, contain fly ash.
[0246] The powder coating composition according to the invention may in principle be applied to a substrate by any process of powder coating technology, for example by electrostatic spray coating (corona charging or tribocharging) or by a fluidized bed process or an electrostatic fluidized bed process.
[0247] After the powder coating composition has been applied to the substrate, the conversion of the resulting deposited particles into a continuous coating (including, where appropriate, the curing of the applied composition) can be carried out by heat treatment and / or by radiant energy, in particular infrared, ultraviolet or electron beam radiation. The powder is usually cured on the substrate by application of heat (stoving process); the powder particles melt and flow and a film is formed. The curing time and temperature are interdependent depending on the formulation of the composition used. The substrate may comprise metal, heat stable plastic material, wood, glass or ceramic or textile material. Advantageously, metal substrates are chemically or mechanically cleaned before application of the composition and are preferably subjected to a chemical pretreatment, for example with iron phosphate, zinc phosphate or chromate. Substrates other than metal are generally preheated before application or, in the case of electrostatic spray application, pretreated with a material that aids such application.
[0248] [Table 2]
[0249] Traffic Sign Coating The coating composition may be suitable for use as a traffic marking coating. A suitable coating composition includes: (a) 1.0wt%-6.0wt% fly ash; (b) 1.0wt%~70wt% TiO2; (c) 20 wt% to 35 wt% water, and (d) 25 wt% to 40 wt% of a polymeric binder material; Here, fly ash is defined as having a d of less than 4.0 μm. 50 It has a particle size.
[0250] Traffic marking coatings can be solvent-based, water-based, hot melt, or catalyzed compositions with or near 100% solids. The major type of traffic marking coating composition is water-based, with the majority of colors being bright white and bright yellow. Although the largest single category is water-based traffic marking paints, the fly ash described in this invention can also be advantageously used in other types of traffic marking coatings. Traffic marking coating compositions typically use high levels of titanium dioxide to provide high levels of opacity and brightness.
[0251] Suitable aqueous traffic marking coating compositions include: (a) 1wt%-60wt% fly ash; (b) 1wt%–70wt% TiO2; (c) 20 wt% to 35 wt% water; and (d) 25 wt% to 40 wt% of polymeric binder material.
[0252] The composition is usually a white or yellow paint. Preferably, the composition is a water-based paint composition for environmental benefits. In some countries, solvent-based traffic marking paint compositions are common and water-based are often more expensive. Preferably, the composition comprises 23wt% to 30wt% water. Preferably, the composition is in the form of an emulsion.
[0253] Preferably, the weight ratio of fly ash to TiO2 ranges from 1:3 to 30:1, preferably from 1:1 to 30:1, or from 1.5:1 to 20:1, or from 2:1 to 10:1, or from 2:1 to 6:1, or from 2:1 to 4:1. Compositions with these weight ratios are optimized for the performance of TiO2 and are extremely environmentally friendly.
[0254] Alternatively, the weight ratio of fly ash to TiO2 can be in the range of 0.6:1 to 1.5:1. Compositions having this weight ratio exhibit good wet scrub resistance and water resistance, and do not easily blister or smear. The weight ratio of fly ash to TiO2 can range from 0.05:1 to 1:1, and even from 0.1:1 to 0.8:1.
[0255] Preferably, the composition comprises between 10wt% and 35wt%, or between 15wt% and 35wt%, or between 20wt% and 35wt%, or between 20wt% and 30wt% of fly ash. Typically, the composition comprises 1 wt% to 30 wt% TiO2, or 5 wt% to 20 wt% TiO2. Preferably, the composition comprises 1 wt% to 8 wt% TiO2, alternatively, the composition may comprise 15 wt% to 30 wt% TiO2.
[0256] Typically, the compositions have a viscosity in the range of 100-500 cps. The viscosity of the coating composition can be adjusted as needed, for example, to accommodate storage stability and / or various application methods (such as spray vs. brush).
[0257] The composition may include other powder materials. The composition may include 0 wt% to 30 wt%, or 1.0 wt% to 27 wt%, or 1.0 wt% to 25 wt%, or 1 wt% to 20 wt%, or 1 wt% to 15 wt% of other powder materials.
[0258] Suitable powder materials include materials that adjust the optical or rheological properties of the composition, and yellow pigments required to impart color. Other powder materials include calcium carbonate. Other powdered materials include barium sulfate, talc, wollastonite, calcium carbonate and / or calcium sulfate, silica, quartz, mica, and any combination thereof. Other suitable powdered materials include calcium silicate and / or dolomite.
[0259] The paint can be brilliant white, but it can also be a pastel-like off-white. Usually, paint is the L of paint (preferably dried paint). * a* b * is defined by the value, where L * is greater than 80, a * and b * are independently within the range of ±10.
[0260] Typically, the composition has a whiteness L value of greater than 80, or greater than 85, or greater than 90, or greater than 95. Typically, the composition is white and the a and b values are each independently in the range of -10.0 to +10.0. Typically, the compositions have a hiding power / contrast ratio of greater than 85.0, or even greater than 90.
[0261] The composition will typically include other ingredients. Any suitable ingredient may be included in the composition. Suitable additional ingredients are described above or below.
[0262] Non-aqueous solvents may also be included in water-based coating compositions. Non-aqueous solvents often have adverse environmental effects if released into the environment during drying. For this reason, there has been an increase in more environmentally friendly "low VOC" (low volatile organic content) or non-VOC coating compositions, such as water-based coating compositions, especially water-based emulsion coating compositions.
[0263] However, some solvents that decompose more readily in the atmosphere and therefore pose much less risk to the environment are regulated as "exempt" solvents that do not have to meet regulatory limits. Preferably, the solvent is an exempt solvent. Examples of exempt solvents include acetone, dimethyl carbonate, methyl acetate, parachlorobenotrifluoride, tert-butyl acetate, propylene carbonate, and any combination thereof. Such exempt solvents can be used at higher levels than non-exempt solvents. Exempt solvents can be used in coating compositions for applications where water-based solvents are not suitable. Examples of other non-aqueous solvents that can be incorporated into the aqueous traffic marking compositions include, but are not limited to, oxygen-containing solvents (e.g., alcohols, ketones, esters, ethers, glycols, glycol ethers, glycol ether esters, ether esters, etc.) such as, but not limited to, methanol, ethanol, propanol, butanol, isobutanol, isopropanol, butyl cellosolve, PM acetate, diacetone alcohol, etc., and hydrocarbons such as, but not limited to, aromatic 100, aromatic 150, aromatic 200, VM&P naphtha, xylene, toluene, etc.
[0264] The solvent not only solubilizes the polymeric binder material, but also serves to adjust viscosity, minimize coating defects, provide flow and leveling, or the solvent can act as a liquid carrier material in which the polymeric binder does not dissolve, but instead forms a stable dispersion of the polymeric binder in the solvent.
[0265] In some cases it may be preferred that the solvent is an organic solvent. The preferred organic solvents are aliphatic hydrocarbons. Aliphatic hydrocarbon solvents are commonly used in oil-based coating compositions. The composition may include 20 wt % to 50 wt % of an organic solvent.The composition may include 20 wt % to 50 wt % of an aliphatic hydrocarbon.
[0266] Preferably, the composition comprises from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of the polymeric binder material. Preferably, the polymeric binder material is selected from carboxylate polymers for water-based systems. The polymeric binder material may be a carboxylate polymer. The preferred binder is a polycarboxylate polymer, which may be modified with styrene, vinyl, or other suitable modifications as described in more detail below, although other binders suitable for water-based traffic marking coatings include alkyds, polyurethane dispersions, polyesters, and the like.
[0267] The polymeric binder material may be an alkyd resin and / or a polyurethane dispersion. Suitable carboxylate polymers are polycarboxylate polymers. The composition may comprise from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of the carboxylate polymer. The composition may include from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of the alkyd resin. Suitable polymeric binder materials are available from Arkema and Dow.
[0268] Particularly preferred polymeric binder materials are carboxylate polymers. Suitable carboxylate polymers include copolymers and / or terpolymers, and suitable polymers include carboxylate polymers that include monomers selected from methanoic acid, ethanoic acid, propanoic acid, butanoic acid, and any combination thereof. Particularly preferred carboxylate polymers include propanoic acid monomers and / or monomers derived from propanoic acid.
[0269] Suitable carboxylate polymers include copolymers and / or terpolymers selected from polyacrylates. Suitable polyacrylates include acrylic or methacrylic acid copolymers, vinyl acrylates, ethylene-vinyl acetate-acrylic acid, styrene-acrylic acid, ethylene-vinyl acetate-acrylate, polyvinyl acetate-polyvinyl chloride-acrylate (PVC / PVAc), and polyacrylates containing monomers selected from methacrylates. Derivatives of these monomers are also suitable for use in polyacrylate polymers.
[0270] Suitable carboxylate polymers are those based on derivatives of acrylic or methacrylic acid, such as polyacrylates including acrylic acid, butyl acrylate, 2-ethylhexyl acrylate and others for special functions / performance, styrene-acrylic polymers, and copolymers of acrylic acid and methacrylic acid.
[0271] Suitable carboxylate polymers include vinyl functional monomers such as vinyl acetate-acrylic copolymers. Suitable carboxylate polymers are Arkema DT 211, Arkema DT 250, Dow Fastrack 2706 and Dow Fastrack 3427.
[0272] Preferably, the polymeric binder is a carboxylate polymer. Preferably, the carboxylate polymer is in the form of a latex emulsion, preferably an aqueous latex emulsion. This is particularly preferred when the solvent is water.
[0273] The carboxylates can be modified with modifying monomers to make vinyl or styrene modified acrylic latexes. A highly preferred polymeric binder material is a carboxylate polymer. Preferably, the composition comprises from 10 wt% to 30 wt%, or from 15 wt% to 30 wt% of a carboxylate polymer. A preferred carboxylate polymer is a polyacrylate polymer or a derivative thereof.
[0274] Carboxylate polymers are usually added to coating compositions in the form of aqueous latex emulsions or dispersions (such as polyurethane dispersions). Such emulsions typically have a solids content of 30 wt% to 60 wt%. The polymer particles in the latex are typically between 100 nm and 1000 nm in size.
[0275] Polycarboxylates, and especially polyacrylates, have excellent physical and chemical properties such as fast drying time, also known as "No-Pick-Up Time", glass bead retention, resistance to water immediately after rainfall, adaptability to a wide range of moisture and temperature conditions, resistance to UV light, abrasion resistance, vapor permeability, high weather resistance, and gloss retention.
[0276] Some carboxylate polymers have dispersant properties and can act as dispersants. Such carboxylate polymers include homopolymers and copolymers of polycarboxylic acids (including those modified to be hydrophobic or hydrophilic), such as polyacrylic acid or polymethacrylic acid or maleic anhydride with various monomers such as styrene, methacrylate, diisobutylene, and other hydrophilic or hydrophobic comonomers. For example, for some components, the level of carboxyl functionality in these oligomers or polymers is so high that they are sufficiently polar to be dispersed in water without the addition of neutralizing amines.
[0277] Preferably, the composition comprises from 10 wt% to 30 wt%, or from 15 wt% to 25 wt% of the carboxylate polymer. A suitable polymeric binder material is an acrylic acid copolymer. A suitable polymeric binder material may include monomers such as acrylic acid, butyl acrylate, 2-ethylhexyl acrylate, and the like.
[0278] How to measure particle size Particle size distribution is usually measured by laser diffraction. A suitable standard for measuring particle size distribution by laser diffraction is given in ASTM B822-20, using 0.5 g of sample powder dispersed in 1 liter of deionized water. Suitable particle size analyzers are Malvern Instruments' Mastersizer 2000 and 3000 instruments. It is preferable to disperse the sample with compressed air (usually using a Scirocco 2000 unit) and test the material as a powder stream, rather than using the wet method where the test material is first dispersed in a fluid. However, it is possible to test these ceramic mixtures dispersed in non-aqueous liquids. Measurements are usually made according to the manufacturer's instructions and test procedures.
[0279] How to measure oil adsorption Oil absorption can be measured according to ASTM D-281-12. The test sample size is 20g. Add a drop of linseed oil to 20g of test material and mix with a spatula until it forms a smooth paste that can be spread evenly on a flat surface. Values are reported as cc of oil required to initially form a paste per 100g of powder.
[0280] How to measure iron oxide content Iron oxide levels are usually measured by X-ray fluorescence. The typical particle size of fly ash is small enough that this technique is suitable for accurate measurement. The technique works by exciting the sample with high-energy gamma or X-ray radiation. This causes the atoms present to ionize and emit EM radiation at a characteristic frequency that depends on the type of atom. Analyzing the intensity of the different frequencies allows for elemental analysis. Suitable instruments include the Varta series of XRF analyzers from Olympus. This device detects the element iron, the results of which are most often converted to the corresponding level of Fe2O3.
[0281] Method for measuring calcium oxide content Calcium oxide levels can be measured by X-ray fluorescence as described in ASTM D4326-21 "Standard Test Method for Major and Minor Elements in Coal Ash by X-Ray Fluoresence". Suitable XRF instruments include Malvern Panalytical's Epsilon 4 XRF analyzer, using sample disks prepared using Claisse's Aegon 2 automatic fusion instrument for sample disk preparation. The ash sample is automatically dissolved in molten lithium borate flux and formed into a disk, which is placed in the Epsilon 4 for analysis. The instrument is operated according to the manufacturer's instructions. For CaO measurements, the Epsilon 4 is set to a voltage of 12 kV, a current of 25 μa, no helium as a medium, a 50 μ Al filter, and a measurement time of 450 seconds.
[0282] How to measure zeta potential Suitable instruments for measuring the zeta potential of materials are the Zetasizer series from Malvern Panalytical (e.g. Zetasizer Lab from the Zetasizer Advance series). The instrument is operated according to the manufacturer's instructions. It is important that the sample concentration is not too high or too low as this can cause attenuation of the beam. A concentration of 0.1% (1 g sample in 1 litre of solution) is suitable for most materials of interest here. NaCl solutions can also be used, a concentration of 0.01 M at pH 7 is suitable. Measurements are performed at ambient temperature conditions.
[0283] Concealment Powder / Method of Measuring Contrast Ratio Opacity can be measured directly by the contrast ratio of a film. The contrast ratio is defined as the ratio of the reflectance of a film on a black substrate to the reflectance of the same film on a white substrate. The reflectance or "Y" is the CIE Y value when the sample is measured on the CIE XYZ scale. Contrast ratio is usually reported as a percentage. Materials with high contrast ratios (>99%) appear visually completely opaque. ASTM D2805-11 "Standard Test Method for Hiding Power of Paints by Reflectometry" describes the procedure to be used. Suitable equipment includes the UltraScan PRO series from Hunterlab, Inc. (Reston, VA), operating in accordance with ASTM E308-18.
[0284] A paint sample is applied to a glass plate and allowed to dry to form a 50 micron (2 mil) thick film onto the glass plate. Reflectance is measured using the glass with a black background and then using the glass with a white background. The contrast ratio is the ratio of the two reflectance values.
[0285] How to measure viscosity Coating viscosity measurements are typically performed using several different test rheometers, given the complex rheology of coatings. ASTM D7394-18 is commonly used and describes the use of three rheometers to cover the range of shear rates of interest when different application methods are considered.
[0286] Low shear viscosity is measured using a Brookfield viscometer with a #3 spindle at 100 rpm. High shear (12000 s-1) viscosity is measured using a cone-and-plate rheometer according to ASTM D4287-00(2019). Medium shear viscosity is measured using a Stormer viscometer operated in accordance with ASTM D562-10(2018). Sag resistance is measured in accordance with D4400-18.
[0287] CIELAB color space value L * 、a * 、b * How to measure The color of a material is generally expressed in the L * , a * , b * It is expressed using coordinates. * The L value represents the degree of whiteness, with an L value of 0 meaning the material is completely black and an L value of 100 meaning the material appears completely white. * The value is green (a * is negative) to red (a * b represents a color up to a positive value. * The scale of blue (negative b * value) to yellow (positive b * Characterize the color up to the L value. * a * b * scale(" * The LAB scale (sometimes called the Lab or LAB scale, since "Lab" is sometimes abbreviated) characterizes colors within the range of human light perception. * a * b * The calculation of the value is carried out according to ASTM standard D2244-21. * a * b * Suitable instruments for measuring values include the UltraScan PRO series from Hunterlab (Reston, VA) which operates in accordance with ASTM E308-18.
[0288] Fly ash preparation process Fly ash is typically whitened prior to incorporation into a coating composition. A suitable process for preparing fly ash, also referred to herein as whitened fly ash, is described below.
[0289] The process includes the following steps: (a) optionally subjecting the fly ash to a particle size classification (sizing) step to obtain sized fly ash having at least 90 wt% having a particle size between 44 μm and 250 μm; (b) optionally contacting the sized fly ash from step (a) with water to form a slurry. wherein the slurry has a solids content of less than 40 wt%; (c) subjecting the sized fly ash obtained in step (a) or the slurry obtained in step (b) to an extensive magnetic separation process to form a magnetically treated fly ash. wherein the exhaustive magnetic separation step comprises a first magnetic extraction step and a second magnetic extraction step, and preferably the second magnetic extraction step is carried out at a higher magnetic field strength than the first magnetic extraction step; (d) subjecting the magnetically treated fly ash obtained in step (c) to a milling step to form a whitened fly ash.
[0290] Step (a), sizing In step (a), the fly ash is subjected to a size classification step to obtain a size-classified fly ash, of which at least 90 wt%, or at least 95 wt%, has a particle size of 44 μm to 250 μm, or 50 μm to 250 μm, or 75 μm to 250 μm. The fly ash is preferably subjected to a size classification step to obtain a size-classified fly ash, of which 100 wt% has a particle size of 44 μm to 250 μm, or 50 μm to 250 μm, or 75 μm to 250 μm. Classification can be carried out in an air classifier.
[0291] While this coarse fly ash is too coarse to be used as a pozzolan, and is often dark due to a high concentration of large unburned carbon particles, it has surprisingly been found to be particularly suitable for purification by magnetic extraction, particularly wet magnetic extraction. The coarser fly ash can be refined to a greater extent by magnetic extraction than the finer fly ash. Without wishing to be bound by theory, it is believed that larger magnetically-susceptible particles experience a greater force in a magnetic field due to the greater amount of magnetically susceptible material present. The amount of material present in a particle of a given diameter is a function of the cube of the diameter. In contrast, the viscous drag force experienced by a particle moving through a liquid is a function of its diameter. Thus, larger magnetically-susceptible particles experience a greater ratio of magnetic to viscous drag forces, thereby allowing for easier removal of the magnetically-susceptible particles from the slurry.
[0292] Optional Step (b), Formation of Slurry Optional step (b) involves contacting the sized fly ash from step (a) with water to form a slurry, the slurry having a solids content of less than 40 wt%, less than 35 wt%, or less than 30 wt%. Preferably, step (b) is an essential step and during step (c), the slurry obtained in step (b) is subjected to an extensive magnetic separation step to form a magnetically treated fly ash.
[0293] Step (c), magnetic extraction Step (c) comprises subjecting the sized fly ash obtained in step (a) or the slurry obtained in step (b) to an extensive magnetic separation process to form a magnetically treated fly ash.
[0294] The exhaustive magnetic separation process includes a first magnetic extraction step and a second magnetic extraction step, the second magnetic extraction step being performed at a higher magnetic field strength than the first magnetic extraction step. Additional magnetic extraction steps may be used, with each subsequent magnetic extraction step typically being carried out at a higher magnetic field strength than the preceding magnetic extraction step. Preferably, a third magnetic extraction step is carried out, with the third magnetic extraction step being carried out at a higher magnetic field strength than the second magnetic extraction step.
[0295] Typically, the magnetically treated fly ash has an iron oxide content of less than 1.0%, or even less than 0.5%. Step (c) uses an exhaustive process of magnetic extraction to remove particles containing very low levels of magnetically susceptible iron-containing species, leaving a residue of highly refined material with very low iron content. This differs from most magnetic separation processes, which are: (i) designed to remove only particles with high iron content for further processing such as metal extraction, and / or (ii) designed for beneficiation of fly ash for use as a pozzolana.
[0296] The process involves exhaustive magnetic extraction steps. By exhaustive, we mean subjecting the slurry to multiple magnetic field extraction steps, where the magnetic field strength is constant or increased during each subsequent step. Typically, the slurry is advanced to the next magnetic field strength extraction step only if the current magnetic field strength (field strength) is unable to extract any more magnetically susceptible material. Subjecting classified fly ash or slurry to a single high intensity magnetic extraction step also removes much of the non-magnetic material, and without wishing to be bound by theory, it is believed that the non-magnetic material is captured by the bulk of the magnetically susceptible material once all of it has been removed.
[0297] The inventors have found that when magnetically susceptible materials are removed by multiple magnetic extraction steps, as required in the process of the present invention, only limited amounts of material are removed in any one step, resulting in an increased overall efficiency of the process and less non-magnetically susceptible material being removed from the classified fly ash or slurry during step (c).
[0298] Step (c) can be carried out by passing a magnetic bar of a predetermined magnetic field strength through the slurry, typically in a slow and controlled manner to avoid removal of particles due to fluid drag, after which the magnetic bar can be removed from the slurry and the magnetically susceptible material attached to the magnetic bar removed.
[0299] Typically, a first magnetic bar with a relatively low magnetic field strength is used until no more magnetically susceptible material is removed with each pass of the magnetic bar through the slurry. Typically, a second magnetic bar with a relatively high magnetic field strength is then used and the magnetic extraction step is repeated. Additional magnetic extraction steps with each step using a magnetic bar with a relatively high magnetic field strength can be used. This process differs from other processes in commercial use in that it is repeated (preferably gently) to extract the magnetically susceptible material (thus "exhausting" the magnetically susceptible material at a given magnetic field strength) before moving on to the next step.
[0300] It is preferred that the solids concentration of the slurry used in the magnetic extraction process is less than 40 wt%, or less than 35 wt%, or even less than 30 wt%, since in high solids slurries particle separation becomes difficult due to particle:particle interactions and collisions.
[0301] Typically, a magnet is passed through the aqueous slurry or the slurry is passed through a magnetic separator. This procedure is typically repeated multiple times, for example, until the magnetically susceptible material is no longer extracted by the magnet. This typically requires a minimum processing time for subjecting the slurry to the magnetic field. If the magnetic processing time is too short, the magnetically susceptible material may not have a sufficient opportunity to be removed. A typical minimum processing time is at least 1 minute, or at least 5 minutes, or even at least 10 minutes, or even more. The duration of processing time may be achieved over multiple steps, such as passing through a magnetic separator at a given magnetic field strength.
[0302] A suitable magnetic treatment may be a 1000 Gauss magnetic bar repeatedly passed through the slurry, then a 3000 Gauss magnetic bar repeatedly passed through the slurry, then an 8000 Gauss or a 10000 Gauss magnetic bar.
[0303] Other types of magnetic separators are also suitable, especially for large-scale industrial processes. A suitable type of separator is the so-called Wet High Intensity Magnetic Separator, where the magnetic particles are removed from the slurry by being magnetically attracted to the surface of a rotating drum by application of a suitable magnetic field. Other suitable designs include cascade magnetic separators, where the slurry flows by gravity over a magnetic surface. There are several designs, but all rely on the material (preferably in a slurry form) passing close to a magnetic surface so that the magnetic particles adhere to the surface. The magnetic particles may be washed away or removed from the surface. The magnetic field may be generated by a permanent magnet (suitably positioned) or by an electromagnet. A preferred method involves the use of one or more magnetic separators with adjustable electromagnets. The slurry may be repeatedly passed through the separator at a given magnetic field strength, and when all the magnetic material has been completely (thoroughly) extracted at that magnetic field strength, the electromagnet is adjusted to increase the magnetic field strength and the process is repeated.
[0304] Alternatively, the slurry can be repeatedly passed through a first separator set at a lower magnetic field strength and then a second separator set at a higher magnetic field strength to achieve a thorough effect. Eriez Corporation (Erie, Pennsylvania, USA) offers a series of suitable magnetic separators.
[0305] The magnetically treated fly ash obtained in step (c) is also preferably subjected to a chemical treatment step, which can be carried out in the presence of a chelating agent, preferably in the presence of both a chelating agent and an acid. Preferred chelating agents include ethylenediaminedisuccinic acid (EDDS), ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), ethylenediaminedi(o-hydroxyphenylacetic acid) (EDDHA), 1-hydroxyethane-1,1 diphosphonic acid (HEDP), hydroxyethylethylenediaminetriacetic acid (HEDTA), and any combination thereof.
[0306] During the optional chelation step, the fly ash is typically contacted with a chelating agent. Typically, the fly ash and the chelating agent are contacted together with water to form an aqueous slurry. The chelation step can be carried out at elevated temperatures, such as greater than 50° C., greater than 60° C., or greater than 70° C. Typically, the liquid supernatant is removed. The remaining fly ash may be rinsed.
[0307] In step (c), the magnetically treated fly ash is preferably subjected to a calcination and / or sintering step. During step (c), the magnetically treated fly ash is preferably subjected to a calcination step, typically at a temperature above 450°C, alternatively above 500°C, alternatively above 600°C, alternatively above 750°C, typically up to 1000°C.
[0308] During step (c), it may be preferred that the magnetically treated fly ash is subjected to a sintering step, typically at above 1000° C., alternatively above 1100° C., alternatively above 1200° C., alternatively above 1300° C. This sintering step may further improve the color of the magnetically treated fly ash and / or reduce the leachability of substances such as heavy metal ions from the magnetically treated fly ash.
[0309] Step (d): Milling Step (d) comprises subjecting the magnetically treated fly ash obtained in step (c) to a pulverizing process to form a whitened fly ash. In step (d), the magnetically treated fly ash obtained in step (c) is subjected to a grinding process to obtain a whitened fly ash. Step (d) can be a wet grinding process or a dry grinding process. A ball mill or a vibrating rod mill are suitable equipment regardless of whether the grinding process is a dry grinding process or a wet grinding process.
[0310] The wet-grinding step may be an acidic wet-grinding step, in which the magnetically treated fly ash obtained in step (c) is contacted with an acid and subjected to the acidic wet-grinding step. Suitable acids for use in step (d) include mineral acids and / or organic acids.
[0311] Suitable acids for use in step (d) may be selected from acetic acid (ethanoic acid), ascorbic acid ((2R)-2-[(1S)-1,2-dihydroxyethyl]-3,4-dihydroxy-2H-furan-5-one), citric acid, hydrochloric acid, nitric acid, oxalic acid (ethanedioic acid), sulfuric acid, and any combination thereof. A preferred acid is sulfuric acid. Another preferred acid is hydrochloric acid.
[0312] Preferably, the acid used in step (d) has a molar concentration of 0.2M to 3.0M, or 0.5M to 2.5M, or even 1.0M to 2.0M. Preferably, step (d) is carried out at a pH below 6.0, or below 5.0, or below 4.0, or below 3.0, or below 2.0, or even below 1.0.
[0313] The acidic wet-grinding step may be carried out in the presence of a chelating agent, suitable chelating agents are described above (Suitable chelating agents for step (c)). Step (d) may be carried out at a temperature of at least 50°C, or even higher than 60°C or even higher than 70°C. The duration of step (d) is 90 minutes or less, for example, from 10 to 90 minutes, or from 20 to 80 minutes, or even from 30 to 70 minutes. Preferably, step (d) is carried out in a ball mill or rod mill.
[0314] The wet grinding step may preferably include a first acidic grinding step and a second acidic grinding step. The acid used in the first acidic grinding step may be the same as the acid used in the second acidic grinding step, or a different acid may be used. It may be preferable that the acid used in the second acidic grinding step has a higher molar concentration than the acid used in the first acidic grinding step. Preferably, the first acidic grinding step is carried out in the presence of hydrochloric acid. Preferably, the second acidic grinding step is carried out in the presence of oxalic acid.
[0315] Preferably, step (d) is carried out at a pH below 6.0, or below 5.0, or below 4.0, or below 3.0, or below 2.0, or even below 1.0. Step (d) may be carried out under pressure above atmospheric pressure. Step (d) may be carried out at a temperature above 100°C, such as above 125°C, or up to 150°C.
[0316] During step (d), it may be preferred that the pulverized magnetically treated fly ash is subjected to a calcination step, typically at temperatures above 450°C, alternatively above 500°C, alternatively above 600°C, alternatively above 750°C, and typically up to 1000°C.
[0317] During step (d), it may be preferred to subject the ground magnetically treated fly ash to a sintering step, typically at above 1000° C., alternatively above 1100° C., alternatively above 1200° C., alternatively above 1300° C. This sintering step may further improve the color of the magnetically treated fly ash and / or reduce the leachability of substances such as heavy metal ions from the magnetically treated fly ash. The sintered fly ash may be further ground.
[0318] EMBODIMENTS OF THE PRESENT DISCLOSURE [1] A coating composition comprising: (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 70 wt% TiO2; and (d) 10 wt% to 80 wt% of a polymeric binder material; Including, Here, the fly ash has a d 50 A composition having a particle size. [2] 2. The composition of embodiment 1, which is a white composition, (a) 3wt%-35wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 50 wt% of a solvent; and (d) 10 wt% to 30 wt% of a polymeric binder material; A composition comprising: [3] Fly ash is less than 12.0 μm d 90 3. The composition of embodiment 2, having a particle size. [4] Fly ash is less than 6.0 μm d 90 The composition according to any one of embodiments 2 to 3, having a particle size. [5] Fly ash is less than 5.0 μm d 90 5. The composition of any one of embodiments 2 to 4, having a particle size.
[0319] [6] Fly ash is less than 4.0 μm d 90 6. The composition of any one of embodiments 2 to 5, having a particle size. [7] Fly ash is less than 3.0 μm d 50 7. The composition of any one of embodiments 2 to 6, having a particle size. [8] Fly ash is in the range of 0.5μm to 3.0μm. 50 8. The composition of any one of embodiments 2 to 7, having a particle size. [9] Fly ash is in the range of 1.0μm to 2.0μm. 509. The composition of any one of embodiments 2 to 8, having a particle size.
[10] 10. The composition of any one of embodiments 2-9, wherein the solvent is water, the polymeric binder material is a carboxylate polymer, and the paint is an emulsion paint.
[0320]
[11] 10. The composition of any one of embodiments 2-9, wherein the solvent is an aliphatic hydrocarbon and the polymeric binder material is an alkyd resin.
[12] 12. The composition according to any one of embodiments 2 to 11, wherein the weight ratio of fly ash to TiO2 ranges from 2:1 to 30:1.
[13] 13. The composition of any one of embodiments 2-12, wherein the fly ash has an oil absorption of less than 40 cc / 100 g.
[14] 14. The composition of any one of embodiments 2-13, wherein the fly ash comprises less than 1.5 wt.% Fe2O3.
[15] 15. The composition of any one of embodiments 2-14, wherein the fly ash contains less than 1.5 wt.% CaO.
[0321]
[16] 16. The composition of any one of embodiments 2 to 15, wherein the fly ash has a zeta potential of -20 mV to -60 mV.
[17] 17. The composition of any one of embodiments 2-16, comprising 15 wt% to 30 wt% of a carboxylate polymer.
[18] The composition of embodiment 17, wherein the carboxylate polymer is polyacrylic acid or a derivative thereof.
[19] 19. The composition of any one of embodiments 2-18, comprising 20 wt% to 35 wt% fly ash.
[20] 20. The composition according to any one of embodiments 2 to 19, comprising 1 wt% to 8 wt% of TiO2.
[0322] [twenty one] 21. The composition of any one of embodiments 2-20, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1. [twenty two] 22. The composition of any one of embodiments 2 to 21, having a viscosity in the range of 400 cP to 1500 cP. [twenty three] 23. The composition of any one of embodiments 2 to 22, wherein the composition has a hiding power / contrast ratio of greater than 99.0. [twenty four] 24. The composition of any one of embodiments 2-23, wherein the composition is an architectural coating composition. [twenty five] 2. The composition of embodiment 1, comprising: (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% water and / or solvent; and (d) 10 wt % to 35 wt % of a polymeric binder material selected from modified or unmodified polyacrylates; A composition comprising:
[0323]
[26] Fly ash is less than 12.0 μm d 90 26. The composition of embodiment 25, having a particle size.
[27] Fly ash is less than 6.0 μm d 90 27. The composition of any one of embodiments 25-26, having a particle size.
[28] Fly ash is less than 5.0 μm d 90 28. The composition of any one of embodiments 25 to 27, having a particle size.
[29] Fly ash is less than 4.0 μm d 90 29. The composition of any one of embodiments 25 to 28, having a particle size.
[30] Fly ash is less than 3.0 μm d 5030. The composition of any one of embodiments 25 to 29, having a particle size.
[0324]
[31] Fly ash is in the range of 0.5μm to 3.0μm. 50 31. The composition of any one of embodiments 25 to 30, having a particle size.
[32] Fly ash is in the range of 1.0μm to 2.0μm. 50 32. The composition of any one of embodiments 25 to 31, having a particle size.
[33] 33. The composition of any one of embodiments 25-32, wherein the composition comprises water and the paint is an emulsion paint.
[34] 34. The composition of any one of embodiments 25-33, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[35] 35. The composition of any one of embodiments 25-34, wherein the fly ash has an oil absorption of less than 40 cc / 100 g.
[0325]
[36] 36. The composition of any one of embodiments 25-35, wherein the fly ash comprises less than 1.5 wt.% Fe2O3.
[37] 37. The composition of any of embodiments 25-36, wherein the fly ash contains less than 1.5 wt.% CaO.
[38] 38. The composition of any one of embodiments 25 to 37, wherein the fly ash has a zeta potential of -20 mV to -60 mV.
[39] 39. The composition of any one of embodiments 25-38, comprising 15 wt% to 30 wt% of a polymeric binder material selected from modified or unmodified polyacrylates.
[40] 40. The composition of any one of embodiments 25-39, comprising 20 wt% to 35 wt% fly ash.
[0326]
[41] 41. The composition of any one of embodiments 25-40, wherein the composition comprises 1 wt% to 8 wt% TiO2.
[42] 42. The composition of any one of embodiments 25-41, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[43] 43. The composition of any one of embodiments 25-42, wherein the composition has a viscosity in the range of 400 cP to 2500 cP.
[44] 44. The composition of any one of embodiments 25 to 43, wherein the composition has a concealing powder / contrast ratio of greater than 98.0.
[45] 45. The composition of any one of embodiments 25-44, wherein the composition is an architectural coating composition.
[0327]
[46] The composition of embodiment 1, which is an aqueous-based composition, (a) 1wt%-50wt% fly ash; (b) 1wt%–30wt% TiO2; (c) 20 wt% to 60 wt% water, and (d) 10 wt% to 35 wt% of a polymeric binder material; A composition comprising:
[47] Fly ash is less than 12.0 μm d 90 47. The composition of embodiment 46, having a particle size.
[48] Fly ash is less than 6.0 μm d 90 48. The composition of any one of embodiments 46-47, having a particle size.
[49] Fly ash is less than 5.0 μm d 90 49. The composition of any one of embodiments 46-48, having a particle size.
[50] Fly ash is less than 4.0 μm d 90 50. The composition of any one of embodiments 46-49, having a particle size.
[0328]
[51] Fly ash is less than 3.0 μm d 50 51. The composition of any one of embodiments 46 to 50, having a particle size.
[52] Fly ash is in the range of 0.5μm to 3.0μm. 50 52. The composition of any one of embodiments 46 to 51, having a particle size.
[53] Fly ash is in the range of 1.0μm to 2.0μm. 50 53. The composition of any one of embodiments 46-52, having a particle size.
[54] 54. The composition of any one of embodiments 46-53, wherein the polymeric binder material is a carboxylate polymer and the paint is an emulsion paint.
[55] 55. The composition of any one of embodiments 46-54, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[0329]
[56] 56. The composition of any one of embodiments 46-55, wherein the fly ash has an oil absorption of less than 40 cc / 100 g.
[57] 57. The composition of any one of embodiments 46-56, wherein the fly ash comprises less than 1.5 wt.% Fe2O3.
[58] 58. The composition of any one of embodiments 46-57, wherein the fly ash contains less than 1.5 wt.% CaO.
[59] The composition of any one of embodiments 46 to 58, wherein the fly ash has a zeta potential of -20 mV to -60 mV.
[60] 60. The composition of any one of embodiments 46-59, comprising 15 wt% to 30 wt% of a carboxylate polymer.
[0330]
[61] The composition of embodiment 60, wherein the carboxylate polymer is polyacrylic acid or a derivative thereof.
[62] 62. The composition of any one of embodiments 46-61, comprising 20 wt% to 35 wt% fly ash.
[63] 63. The composition of any one of embodiments 46-62, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[64] 64. The composition of any one of embodiments 46-63, having a viscosity in the range of 400 cP to 2500 cP.
[65] 65. The composition of any one of embodiments 46 to 64, wherein the composition has a hiding power / contrast ratio of greater than 98.0.
[0331]
[66] 66. The composition of any one of embodiments 46-65, wherein the composition is an architectural coating composition.
[67] 2. The composition of embodiment 1, wherein the composition is a solvent-based composition; (a) 1.0wt%-40wt% fly ash; (b) 1.0 wt% to 60 wt% TiO2 or other pigment; (c) 1.0 wt% to 70 wt% organic solvent; (d) 15 wt% to 80 wt% of a polymeric binder material; and (e) 3.0 wt% to 20 wt% crosslinker; A composition comprising:
[68] Fly ash is less than 12.0 μm d 90 The composition of embodiment 67, having a particle size.
[69] Fly ash is less than 6.0 μm d 90 69. The composition of any one of embodiments 67-68, having a particle size.
[70] Fly ash is less than 5.0 μm d 90 70. The composition of any one of embodiments 67-69, having a particle size.
[0332]
[71] Fly ash is less than 4.0 μm d 9071. The composition of any one of embodiments 67-70, having a particle size.
[72] Fly ash is less than 3.0 μm d 50 72. The composition of any one of embodiments 67-71, having a particle size.
[73] Fly ash is in the range of 0.5μm to 3.0μm. 50 73. The composition of any one of embodiments 67-72, having a particle size.
[74] Fly ash is in the range of 1.0μm to 2.0μm. 50 74. The composition of any one of embodiments 67-73, having a particle size.
[75] 75. The composition of any one of embodiments 67-74, wherein the polymeric binder material is a hydroxy-functional polymer.
[0333]
[76] 76. The composition of any one of embodiments 67-75, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[77] 76. The composition of any one of embodiments 67-75, wherein the fly ash has an oil absorption of less than 40 cc / 100 g.
[78] 78. The composition of any of embodiments 67-77, wherein the fly ash comprises less than 1.5 wt.% Fe3O2.
[79] 79. The composition of any of embodiments 67-78, wherein the fly ash contains less than 1.5 wt.% CaO.
[80] 80. The composition of any one of embodiments 67-79, wherein the fly ash has a zeta potential of -20 mV to -60 mV.
[0334]
[81] 81. The composition of any one of embodiments 67-80, wherein the composition comprises 15 wt% to 50 wt% of the polyester polymer.
[82] The composition of embodiment 81, wherein the polyester polymer is a hydroxy-functional polymer.
[83] 83. The composition of any one of embodiments 67-82, wherein the composition comprises 3.0 wt % to 20 wt % of a crosslinking agent selected from an aminoplast crosslinker and / or a blocked isocyanate crosslinker.
[84] 84. The composition of any one of embodiments 67-83, comprising 20 wt% to 35 wt% fly ash.
[85] 85. The composition of any one of embodiments 67-84, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[0335]
[86] 86. The composition of any one of embodiments 67-85, wherein the weight ratio of fly ash to total pigment is from 4:1 to 0.2:1.
[87] The composition of any one of embodiments 67-86, wherein the composition has a viscosity in the range of 400 cP to 2500 cP.
[88] 88. The composition of any one of embodiments 67 to 87, wherein the composition has a hiding power / contrast ratio of greater than 98.
[89] 89. The composition of any one of embodiments 67-88, wherein the composition is a coil coating paint composition.
[90] 2. The composition of embodiment 1, wherein the composition is a powder coating composition; (a) 10wt%-40wt% fly ash; (b) 1wt%–60wt% TiO2; (c) 15 wt% to 80 wt% of a polymeric binder material; and (d) 3.0 wt% to 20 wt% crosslinker; A composition comprising:
[0336]
[91] Fly ash is less than 12.0 μm d 90 The composition of embodiment 90, having a particle size.
[92] Fly ash is less than 6.0 μm d 90 92. The composition of any one of embodiments 90-91, having a particle size.
[93] Fly ash is less than 5.0 μm d 90 93. The composition of any one of embodiments 90-92, having a particle size.
[94] Fly ash is less than 4.0 μm d 90 94. The composition of any one of embodiments 90-93, having a particle size.
[95] Fly ash is less than 3.0 μm d 50 95. The composition of any one of embodiments 90-94, having a particle size.
[0337]
[96] Fly ash is in the range of 0.5μm to 3.0μm. 50 96. The composition of any one of embodiments 90-95, having a particle size.
[97] Fly ash is in the range of 1.0μm to 2.0μm. 50 The composition of any one of embodiments 90-86, having a particle size.
[98] 98. The composition of any one of embodiments 90-97, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[99] 99. The composition of any one of embodiments 90-98, wherein the fly ash has an oil absorption of less than 40 cc / 100 g.
[0100] 100. The composition of any of embodiments 90-99, wherein the fly ash comprises less than 1.5 wt.% Fe2O3.
[0338]
[0101] 101. The composition of any of embodiments 90-100, wherein the fly ash contains less than 1.5 wt.% CaO.
[0102] The composition of any one of embodiments 90-101, wherein the fly ash has a zeta potential of -20 mV to -60 mV.
[0103] 103. The composition of any one of embodiments 90-102, wherein the composition comprises 15 wt% to 80 wt% of the polyester polymer.
[0104] The composition of embodiment 103, wherein the polyester polymer is a carboxyl functional polymer.
[0105] The composition of embodiment 104, wherein the polymeric binder material is a carboxyl-functional polymer cured with triglycidyl isocyanurate or a hydroxyalkylamide crosslinker.
[0339]
[0106] 106. The composition of any one of embodiments 90-105, comprising 3.0 wt % to 20 wt % of a crosslinking agent selected from triglycidyl isocyanurate and / or a hydroxyalkylamide crosslinking agent.
[0107] 107. The composition of any one of embodiments 90-106, comprising 20 wt% to 35 wt% fly ash.
[0108] 108. The composition of any one of embodiments 90-107, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[0109] 109. The composition of any one of embodiments 90-108, wherein the weight ratio of fly ash to total pigment is from 0.2:1 to 4:1.
[0110] The composition of any one of embodiments 90 to 109, wherein the composition has a hiding power / contrast ratio of greater than 98.
[0340]
[0111] 111. The composition of any one of embodiments 90-110, wherein the composition is a powder coating paint composition.
[0112] 2. The composition of embodiment 1, comprising: (a) 1.0wt%-60wt% fly ash; (b) 1.0wt%~70wt% TiO2; (c) 20 wt% to 35 wt% water; and (d) 25 wt% to 40 wt% of a polymeric binder material; A composition comprising:
[0113] Fly ash is less than 12.0 μm d 90 The composition of embodiment 112, having a particle size.
[0114] Fly ash is less than 6.0 μm d 90 114. The composition of any one of embodiments 112-113, having a particle size.
[0115] Fly ash is less than 5.0 μm d 90 115. The composition of any one of embodiments 112-114, having a particle size.
[0341]
[0116] Fly ash is less than 4.0 μm d 90 116. The composition of any one of embodiments 112-115, having a particle size.
[0117] Fly ash is less than 3.0 μm d 50 117. The composition of any one of embodiments 112-116, having a particle size.
[0118] Fly ash is in the range of 0.5μm to 3.0μm. 50 118. The composition of any one of embodiments 112-117, having a particle size.
[0119] Fly ash is in the range of 1.0μm to 2.0μm. 50 119. The composition of any one of embodiments 112-118, having a particle size.
[0120] 120. The composition of any one of embodiments 112-119, wherein the polymeric binder material is an aqueous dispersion or emulsion of a carboxylate polymeric binder.
[0342]
[0121] Fly ash is less than 4.0 μm d 50 121. The composition of any one of embodiments 112-120, having a particle size.
[0122] 122. The composition of any one of embodiments 112-121, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[0123] 123. The composition of any one of embodiments 112-122, wherein the fly ash has an oil absorption of less than 40 cc / 100 g.
[0124] 124. The composition of any of embodiments 112-123, wherein the fly ash comprises less than 1.5 wt.% Fe2O3.
[0125] 125. The composition of any one of embodiments 112-124, wherein the fly ash contains less than 1.5 wt.% CaO.
[0343]
[0126] 126. The composition of any one of embodiments 112-125, wherein the fly ash has a zeta potential of -20 mV to -60 mV.
[0127] 127. The composition of any one of embodiments 112-126, wherein the composition comprises 15 wt% to 80 wt% of the carboxylate polymeric binder.
[0128] The composition of embodiment 127, wherein the carboxylate polymer is in the form of an emulsion or dispersion.
[0129] 129. The composition of any one of embodiments 112-128, wherein the composition comprises 20 wt% to 35 wt% fly ash.
[0130] 130. The composition of any one of embodiments 112-129, wherein the weight ratio of fly ash to TiO2 ranges from 0.05:1 to 1:1.
[0344]
[0131] 131. The composition of any one of embodiments 112-130, wherein the weight ratio of fly ash to total pigment is from 0.2:1 to 4:1.
[0132] 132. The composition of any one of embodiments 112-131, wherein the composition has a hiding power / contrast ratio of greater than 98.
[0133] 133. The composition of any one of embodiments 112-132, wherein the composition is a traffic marking paint composition.
[0345] [Example] Fly ash preparation method The fly ash was prepared as follows. The whiteness value of the starting PCC fly ash was 25 according to ISO 3688. 200 g of PCC fly ash sieved between 44 μm and 250 μm was added to 2000 g of water and stirred to form a slurry.
[0346] This slurry was then subjected to an exhaustive magnetic extraction and purification process: a 1000 Gauss bar magnet was manually passed repeatedly through the slurry to collect magnetic particles, and wiped off periodically. This was continued until no further magnetic particles were collected on the surface of the magnet. The process was then repeated with a 3000 Gauss bar magnet, and finally using a high-strength 8000 Gauss bar magnet.
[0347] After the magnetic extraction step, the slurry was allowed to settle and the supernatant was discarded. The treated fly ash was dried in an oven at 110°C for 1 hour.
[0348] Next, 150 g of the treated fly ash was placed in a ball mill vessel (fit for MITR model YXQM-8L) along with 150 g of 1.0 M sulfuric acid. Approximately 1250 g of alumina grinding balls were also placed in the vessel. The particle size distribution of the alumina balls (density 3.95 g / ml) was as follows: 5 mm (50 wt%), 10 mm (32 wt%), 20 mm (18 wt%).
[0349] The slurry was then milled in a planetary ball mill (MITR model YXQM-8L) at 180 rpm for 60 minutes, at the end of which the temperature of the slurry was approximately 80°C.
[0350] After milling, the slurry was centrifuged and the supernatant liquid was discarded. The solids were rinsed by adding 300 g of water to the solids with stirring, followed by centrifugation to remove the liquid. This rinsing process was repeated three times. The wet solids were then dried at 110° C. to constant weight. The dried solid was then calcined in an oven at 1250°C for 0.5 hours. The whitened fly ash had a whiteness value of greater than 86 according to ISO 3688. Fly ash d 50 The particle size was less than 4.0 μm.
[0351] Paint sample preparation and characterization Model eggshell paint compositions containing different percentages of TiO2 pigment and fly ash were prepared as follows. of fly ash used 50 The particle size is 1.56 microns, d 90 The particle size was 3.36 microns. The oil adsorption value of this material was 33.5 g oil / 100 g. The Fe2O3 level was 0.33 wt% and the CaO level was 0.1 wt%. The zeta potential when dispersed in water was -37.91 mV.
[0352] Grind stage mixes containing TiO2 (Ti-Pur R-906) and fly ash were prepared as follows: The TiO2 to fly ash ratio was kept constant at 73.4% of the grind stage mix, and the ratio of TiO2 to fly ash was varied.
[0353] A typical let-down stage mix was prepared containing a water-based styrene-acrylic emulsion latex (Carboset CR-3090) and other additives. The let-down stage mix was then added to the grind stage mix to create a series of coating compositions with the same composition in terms of total fly ash and TiO2, but different ratios of fly ash and TiO2 pigment.
[0354] [Table 3]
[0355] Various grind stage mixes were prepared by milling and each was mixed with a let-down stage mix using a Dipermat high speed disperser to a Hegman gauge fineness of 5.5-6.0. The let-down stage mixes were prepared by blending the following materials:
[0356] [Table 4]
[0357] Each grind stage mix was then combined with the let-down stage mix to obtain paint mixtures (A–C) with the following compositions, differing only in the ratio of TiO2 to fly ash, but with a constant total of fly ash and TiO2:
[0358] [Table 5]
[0359] The solids content of the Carboset CR-3090 styrene-acrylic emulsion was 45% (quite typical for this type of latex emulsion), and because some of the additives were liquid, the total solids content of all mixtures was 56.5%. The pH values of the mixtures ranged from 9.1 to 9.2. The mixture was tested for various properties with the following results:
[0360] [Table 6] This indicates that the mixture of fly ash and TiO2 can have a contrast ratio (i.e., opacity) comparable to that of pure TiO2.
[0361] [Table 7] This indicates that the inclusion of fly ash has a significant advantage against physical wear compared to pure TiO2.
[0362] 3 - Dry Rub Test The benefits of TiO2 / fly ash blends were also shown in dry abrasion tests using the Taber abrasion test (ASTM D4060), which measures the amount of material lost from a paint surface after a certain number of abrasion cycles. Although the results are all low (the material is very abrasion resistant), there are benefits to using TiO2 and fly ash blends. Taber Abrasion ASTM D4060 (100 cycles, CR17 wheel, 1000g load)
[0363] [Table 8]
[0364] 4 - Color Characterization of 50 Micron Thick Films This test shows that the blend of TiO2 and fly ash has suitable color properties for use as a white paint. [Table 9]
[0365] Real-life examples [Table 10]
[0366] [Table 11]
[0367] [Table 12]
[0368]
Table 13
[0369]
Table 14
Claims
1. A coating composition comprising: (a) 1.0 wt% to 40 wt% fly ash; (b) 1.0 wt% to 60 wt% TiO 2 and (c) 10 wt% to 80 wt% of a polymeric binder material wherein the fly ash is d less than 4.0 μm 50 A composition having a particle size.
2. The composition according to claim 1, which is a white composition, (a) 3 wt% to 35 wt% fly ash; (b) 1 wt% to 30 wt% TiO 2 ; (c) 20% to 50% by weight of a solvent; and (d) 10 wt% to 30 wt% of a polymeric binder material. A composition comprising:
3. 2. The composition of claim 1 , (a) 1 wt% to 50 wt% fly ash; (b) 1 wt% to 30 wt% TiO 2 ; (c) 20% to 60% by weight of water and / or solvent; and (d) 10 wt % to 35 wt % of a polymeric binder material selected from modified or unmodified polyacrylates. A composition comprising:
4. The composition according to claim 1, which is an aqueous-based composition, (a) 1 wt% to 50 wt% fly ash; (b) 1 wt% to 30 wt% TiO 2 ; (c) 20% to 60% by weight of water; and (d) 10 wt% to 35 wt% of a polymeric binder material. A composition comprising:
5. 10. The composition of claim 1, which is a solvent-based composition, (a) 1.0 wt% to 40 wt% fly ash; (b) 1.0 wt% to 60 wt% TiO 2 or other pigments; (c) 1.0 wt % to 70 wt % of an organic solvent; (d) 15 wt.% to 80 wt.% of a polymeric binder material; and (e) 3.0 wt% to 20 wt% of a crosslinking agent A composition comprising:
6. 10. The composition of claim 1, which is a powder coating composition, (a) 10 wt% to 40 wt% fly ash; (b) 1 wt% to 60 wt% TiO 2 ; (c) 15 wt.% to 80 wt.% of a polymeric binder material; and (d) 3.0 wt% to 20 wt% of a crosslinking agent A composition comprising:
7. 2. The composition of claim 1 , (a) 1.0 wt% to 60 wt% fly ash; (b) 1.0 wt% to 70 wt% TiO 2 ; (c) 20 wt.% to 35 wt.% water; and (d) 25 wt% to 40 wt% of a polymeric binder material. A composition comprising:
8. Fly ash is less than 6.0μm d 90 The composition of any one of claims 1 to 7, having a particle size.
9. Fly ash is less than 5.0μm d 90 The composition of any one of claims 1 to 8, having a particle size.
10. Fly ash is less than 4.0μm d 90 The composition of any one of claims 1 to 9, having a particle size.
11. Fly ash is less than 3.0 μm d 50 The composition of any one of claims 1 to 10, having a particle size.
12. Fly ash is a material with a particle size ranging from 0.5 μm to 3.0 μm. 50 The composition of any one of claims 1 to 11, having a particle size.
13. Fly ash is in the range of 1.0μm to 2.0μm d 50 The composition of any one of claims 1 to 12, having a particle size.
14. The composition according to any one of claims 1 to 13, wherein the fly ash has an oil absorption of 20cc / 100g to 40cc / 100g.
15. Fly ash and TiO 2 The composition according to any one of claims 1 to 14, wherein the weight ratio of:
16. Fly ash is 0.1μm to 1.5μm d 10 The composition of any one of claims 1 to 15, having a particle size.